Secondary battery
Patent Information
- Application Number
- JP2020115876
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-07-03
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2040-07-03
AI Technical Summary
【0036】 本発明の一態様の正極活物質は、電界緩和領域を形成することにより、高い充電電圧、例えばリチウム金属の電位を基準として4.3V以上、好ましくは4.65V乃至4.8V程度の高電圧での充電を可能とすることができる。従って短時間での充電を可能とする蓄電装置を実現できる。さらに、本発明の一態様の正極活物質においては、電界緩和領域を形成することにより、高電圧での充放電を繰り返しても結晶構造が崩れにくく、信頼性が高い。従って、充放電電圧の高い二次電池を実現でき、安全性または信頼性の高い二次電池を実現できる。
Smart Images

Figure 0007638634000001 
Figure 0007638634000002 
Figure 0007638634000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a secondary battery using a positive electrode active material and a method for producing the same, or to a portable information terminal, a vehicle, etc. having a secondary battery.
[0002] One embodiment of the present invention relates to an object, a method, or a manufacturing method. Alternatively, the present invention relates to a process, a machine, a manufacture, or a composition of matter. One embodiment of the present invention relates to a semiconductor device, a display device, a light-emitting device, a power storage device, a lighting device, an electronic device, or a manufacturing method thereof.
[0003] In this specification, the term "electronic device" refers to any device having a power storage device, and an electro-optical device having a power storage device, an information terminal device having a power storage device, and the like are all classified as electronic devices.
[0004] In this specification, the term "power storage device" refers to elements and devices in general that have a power storage function, including, for example, power storage devices such as lithium ion secondary batteries (also called secondary batteries), lithium ion capacitors, and electric double layer capacitors. [Background technology]
[0005] In recent years, various types of power storage devices, such as lithium-ion secondary batteries, lithium-ion capacitors, and air batteries, have been actively developed. In particular, the demand for high-output, high-energy-density lithium-ion secondary batteries has rapidly expanded in conjunction with the development of the semiconductor industry, for example, in portable information terminals such as mobile phones, smartphones, and notebook computers, portable music players, digital cameras, medical equipment, and next-generation clean energy automobiles such as hybrid vehicles (HVs), electric vehicles (EVs), and plug-in hybrid vehicles (PHVs), and has become indispensable in the modern information society as a repeatedly rechargeable energy source.
[0006] In both mobile and vehicle applications, there is a high demand for secondary batteries with large discharge capacity per weight and excellent cycle characteristics. In order to meet these demands, active improvements have been made to the positive electrode active material of the positive electrode of secondary batteries (e.g., Patent Document 1 and Patent Document 2).
[0007] Lithium-ion secondary batteries have problems with charging and discharging at low or high temperatures. Because secondary batteries are power storage means that utilize chemical reactions, it is difficult for them to perform adequately at low temperatures, especially below freezing. In addition, lithium-ion secondary batteries may have a shorter lifespan at high temperatures and may be subject to abnormalities.
[0008] Characteristics required of secondary batteries include safety in various operating environments and improved long-term reliability.
[0009] Furthermore, it is also desirable to be able to charge quickly in order to shorten the charging time. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2018-110065 A [Patent Document 2] JP 2018-206747 A Summary of the Invention [Problem to be solved by the invention]
[0011] Lithium ion secondary batteries and positive electrode active materials used therein have room for improvement in various aspects, such as charge / discharge capacity, cycle characteristics, reliability, safety, and cost.
[0012] Another object of one embodiment of the present invention is to provide a secondary battery that can be used in a wide temperature range and is not easily affected by the environmental temperature.
[0013] An object of one embodiment of the present invention is to provide a positive electrode active material with large charge / discharge capacity.
[0014] Another object of the present invention is to provide a positive electrode active material having a high charge / discharge voltage, to provide a positive electrode active material that is less susceptible to deterioration, or to provide a novel positive electrode active material.
[0015] Another object of the present invention is to provide a secondary battery having a large charge / discharge capacity. Another object of the present invention is to provide a secondary battery having a high charge / discharge voltage. Another object of the present invention is to provide a secondary battery with high safety or reliability. Another object of the present invention is to provide a secondary battery with little deterioration. Another object of the present invention is to provide a secondary battery with a long life. Another object of the present invention is to provide a new secondary battery.
[0016] Another object of one embodiment of the present invention is to provide a novel substance, an active material, a power storage device, or a manufacturing method thereof.
[0017] Note that the description of these problems does not preclude the existence of other problems. Note that one embodiment of the present invention does not necessarily solve all of these problems. Note that it is possible to extract problems other than these from the description of the specification, drawings, and claims. [Means for solving the problem]
[0018] In order to solve the above-mentioned problems, it is desirable to realize a positive electrode active material that is stable over a long period of time and is electrochemically stable at high potential. The active material layer in a secondary battery is mainly composed of a plurality of active material particles, a plurality of conductive materials, and an electrolyte disposed therebetween. The deterioration caused by the charge and discharge of a secondary battery can be considered to be due to a strong potential difference occurring between the active material particles and the electrolyte adjacent to the active material particles. Therefore, a secondary battery that is electrochemically stable at high potential is realized by forming an electric field relaxation region between the positive electrode active material lithium cobalt oxide (also called LCO) and the electrolyte.
[0019] In order to form an electric field relaxation region between the positive electrode active material particles and the electrolyte, a part of the positive electrode active material particles is made of a material capable of having ferroelectricity, or a material capable of having ferroelectricity is provided as a shell (also called a shell) covering the surface of the positive electrode active material particles. In this way, it can be said that the extremely important technical idea of the present invention is to provide a material capable of having ferroelectricity inside or outside the positive electrode active material to relax the electric field. The secondary battery of the present invention has a positive electrode, an electrolyte, and a negative electrode, the positive electrode has a positive electrode active material, and a part of the positive electrode active material has an electric field relaxation region.
[0020] The invention disclosed in this specification is a secondary battery having a positive electrode, an electrolyte, and a negative electrode, in which the positive electrode has a positive electrode active material, the positive electrode active material has an interior, a first region near the surface, and a second region in contact with a part of the first region, the first region having one or both of fluorine and magnesium, and the second region having one or more elements selected from hafnium (Hf), zirconium (Zr), yttrium (Y), barium (Ba), titanium (Ti), lead (Pb), scandium (Sc), strontium (Sr), bismuth (Bi), and tantalum (Ta).
[0021] Furthermore, aluminum, nickel, titanium, etc. may be added to the first region. Another aspect of the present invention is a secondary battery having a positive electrode, an electrolyte, and a negative electrode, in which the positive electrode has a positive electrode active material, and the positive electrode active material has an interior, a first region near the surface, and a second region in contact with a part of the first region, the first region having one or more elements selected from fluorine, magnesium, aluminum, nickel, and titanium, and the second region having one or more elements selected from hafnium (Hf), zirconium (Zr), yttrium (Y), barium (Ba), titanium (Ti), lead (Pb), scandium (Sc), strontium (Sr), bismuth (Bi), and tantalum (Ta).
[0022] In one or both of the first region and the second region, hafnium oxide, zirconium oxide, HfZrO X (X>0), yttria-stabilized zirconia (YSZ), barium titanate, PbTiO X , lead zirconate titanate (PZT), barium strontium titanate (BST), strontium titanate, and strontium bismuthate tantalate may be formed.
[0023] In each of the above configurations, the first region and the second region form a mixed region or an alloy region.
[0024] In each of the above structures, one or both of the first region and the second region can function as an electric field relaxation region.
[0025] In each of the above configurations, one or both of the first region and the second region may be configured to cover a part or the whole of the inside.
[0026] In each of the above configurations, either or both of the first region and the second region may be configured to be scattered in an island shape near the surface of the positive electrode active material.
[0027] In each of the above configurations, either or both of the first region and the second region have ferroelectricity, which is a physical property in which, when the material in question is a dielectric, electric dipoles are aligned within the dielectric in the absence of an electric field outside the dielectric, and the direction of the electric dipoles reversibly changes along the electric field applied to the dielectric.
[0028] In addition, in each of the above configurations, either or both of the first region and the second region have, relative to the interior, a third region having a high dielectric constant and a fourth region having a lower dielectric constant than the third region.
[0029] In this specification, the dielectric constant is measured and calculated in accordance with JIS2141. The dielectric constant is measured using a bridge-type dielectric constant measuring device. The capacitance of a capacitor with two parallel plates facing each other at a distance d and an area S is proportional to S / d. If the proportional constant is ε, the capacitance C of the capacitor can be expressed as εS / d, and the proportional constant ε is called the dielectric constant. Furthermore, the relative dielectric constant refers to the ratio of the dielectric constants of two media. If the dielectric constant of a first medium is ε1 and the dielectric constant of a second medium is ε2, then the relative dielectric constant of the second medium relative to the first medium, ε r is expressed as ε2 / ε1.
[0030] However, the above-mentioned JIS2141 dielectric constant value is a value measured as an aggregate of powder with a certain degree of particle size, and is not suitable for the case of the positive electrode active material disclosed in this specification, which has a portion with a different dielectric constant. However, it is possible to compare and evaluate the dielectric constant value of the aggregate of particles before forming the electric field relaxation region with the dielectric constant value of the aggregate of particles after forming the electric field relaxation region, and it is also possible to perform elemental analysis of a specific position of the cross section of the particle before forming the electric field relaxation region and the particle after forming the electric field relaxation region. Therefore, if there is a difference in the dielectric constant of the aggregate of particles before and after forming the electric field relaxation region, it is also possible to roughly calculate the dielectric constant of the electric field relaxation region provided on the particle.
[0031] In each of the above configurations, the inner portion is one or more composite oxides selected from the group consisting of lithium, cobalt, manganese, nickel, aluminum, and iron. For example, Li-Co oxide (also called LCO) can be used for the inner portion. For example, LiNi x Co y Mn zIt is possible to use NiCoMn-based (also referred to as NCM) represented by O2 (x > 0, y > 0, z > 0, 0.8 < x + y + z < 1.2). Specifically, for example, it is preferable to satisfy 0.1x < y < 8x and 0.1x < z < 8x. As an example, x, y, and z preferably satisfy x:y:z = 1:1:1 or values in the vicinity thereof. Or as an example, x, y, and z preferably satisfy x:y:z = 5:2:3 or values in the vicinity thereof. Or as an example, x, y, and z preferably satisfy x:y:z = 8:1:1 or values in the vicinity thereof. Or as an example, x, y, and z preferably satisfy x:y:z = 9:0.5:0.5 or values in the vicinity thereof. Or as an example, x, y, and z preferably satisfy x:y:z = 6:2:2 or values in the vicinity thereof. Or as an example, x, y, and z preferably satisfy x:y:z = 1:4:1 or values in the vicinity thereof.
[0032] In addition, in each of the above configurations, one or more of the positive electrode, the electrolyte, and the negative electrode have graphene. Further, it is preferable to adopt a configuration in which graphene is fixed so as to surround the surface of the positive electrode active material particles or the surface of the negative electrode active material particles to enhance conductivity. Further, it is preferable to include fluorine in a part of the graphene.
[0033] Since graphene has electrically, mechanically, or chemically amazing properties, it is a carbon material expected to be applied in various fields such as field effect transistors and solar cells using graphene.
[0034] In this specification, graphene has a carbon hexagonal lattice structure and includes single-layer graphene or multi-layer graphene of 2 layers or more and 100 layers or less. Single-layer graphene (one graphene) refers to sp 2A graphene is a sheet of carbon molecules of one atomic layer having bonds. When referring to multiple graphenes, it refers to multi-layer graphene or multiple single-layer graphenes. Graphene is not limited to being composed of carbon only, and may be partially bonded to oxygen, hydrogen, or functional groups, and may be called a graphene compound. Graphene compounds may have excellent electrical properties such as high conductivity, and excellent physical properties such as high flexibility and high mechanical strength. Graphene compounds have a planar shape. Graphene compounds enable surface contact with low contact resistance. Even when they are thin, they may have very high conductivity, and a small amount of them can efficiently form a conductive path in the active material layer. Graphene may be formed by performing a reduction treatment on graphene oxide.
[0035] In addition, the graphene compound can also function as a binder that binds active materials together. Therefore, the amount of binder can be reduced or no binder can be used, and the ratio of active materials to the volume or weight of the electrode can be improved. In other words, the capacity of the secondary battery can be increased. Effect of the Invention
[0036] By forming an electric field relaxation region, the positive electrode active material of one embodiment of the present invention can be charged at a high charging voltage, for example, at a high voltage of 4.3 V or more, preferably about 4.65 V to 4.8 V based on the potential of lithium metal. Therefore, a power storage device that can be charged in a short time can be realized. Furthermore, by forming an electric field relaxation region in the positive electrode active material of one embodiment of the present invention, the crystal structure is not easily broken even when charging and discharging at a high voltage is repeated, and the reliability is high. Therefore, a secondary battery with a high charging and discharging voltage can be realized, and a secondary battery with high safety or reliability can be realized.
[0037] In the positive electrode active material of one embodiment of the present invention, lithium ions are easily inserted into or removed from the positive electrode active material particles even in a low temperature range by forming an electric field relaxation region. Therefore, the secondary battery can be used in a wide temperature range, specifically, in a range of from -40°C to 150°C. Therefore, even if the temperature outside a vehicle equipped with the secondary battery of one embodiment of the present invention is from -40°C to less than 25°C or from 25°C to 85°C, the vehicle can be driven using the secondary battery as a power source. [Brief description of the drawings]
[0038] [Figure 1] FIG. 1A is a cross-sectional view of a positive electrode active material 100, FIG. 1B is a cross-sectional view of a positive electrode active material 104 which is another variation, and FIG. 1B is a partial cross-sectional view of a positive electrode active material 105 which is another variation. [Diagram 2] 2(A), (B1) and (B2) are partial cross-sectional views of the positive electrode active material. [Diagram 3] 3A1, 3A2, 3B1, 3B2, 3C1, and 3C2 are cross-sectional views of parts of the positive electrode active material. [Figure 4] FIG. 4(A) is an example of a schematic diagram of the vicinity of a current collector when a secondary battery is produced using positive electrode active material 100 and charged, and FIG. 4(B) is a cross-sectional schematic diagram showing the state of the secondary battery during charging. [Diagram 5] FIG. 4(A) is a top view of the positive electrode active material, and FIG. 4(B) and FIG. 4(C) are cross-sectional views of the positive electrode active material. [Figure 6] FIG. 6 is a diagram illustrating a method for producing the positive electrode active material 100. [Figure 7] Figure 7(A) is a surface SEM image of the positive electrode active material, and Figures 7(B) and (C) are cross-sectional STEM images of the positive electrode active material. [Figure 8] 8(A) to (G) are EDX mapping images of the positive electrode active material. [Figure 9] FIG. 9 is a diagram illustrating the charge depth and the crystal structure of a positive electrode active material according to one embodiment of the present invention. [Figure 10] FIG. 10 is the XRD pattern calculated from the crystal structure. [Figure 11] FIG. 11 is a diagram illustrating the charge depth and the crystal structure of the positive electrode active material of the comparative example. [Figure 12] FIG. 12 is the XRD pattern calculated from the crystal structure. [Figure 13] FIG. 13 is a graph showing the cycle characteristics of a secondary battery using the positive electrode active material according to this embodiment. [Figure 14] FIG. 14(A) is an exploded perspective view of a coin-type secondary battery, FIG. 14(B) is a perspective view of the coin-type secondary battery, and FIG. 14(C) is a cross-sectional perspective view thereof. [Figure 15] Fig. 15(A) shows an example of a cylindrical secondary battery. Fig. 15(B) shows an example of a cylindrical secondary battery. Fig. 15(C) shows an example of multiple cylindrical secondary batteries. Fig. 15(D) shows an example of a power storage system having multiple cylindrical secondary batteries. [Figure 16] 16(A) and 16(B) are diagrams for explaining an example of a secondary battery, and FIG. 16(C) is a diagram showing the inside of the secondary battery. [Figure 17] 17(A), 17(B), and 17(C) are diagrams illustrating examples of secondary batteries. [Figure 18] 18(A) and 18(B) are diagrams showing the external appearance of a secondary battery. [Figure 19] 19(A), 19(B), and 19(C) are diagrams illustrating a method for manufacturing a secondary battery. [Figure 20] FIG. 20(A) shows an example of the configuration of a battery pack, FIG. 20(B) shows an example of the configuration of a battery pack, and FIG. 20(C) shows an example of the configuration of a battery pack. [Figure 21] 21(A) and (B) are diagrams illustrating an example of a secondary battery. [Figure 22] 22(A), (B), and (C) are diagrams illustrating an example of a secondary battery. [Diagram 23] 23(A) and (B) are diagrams illustrating an example of a secondary battery. [Figure 24]FIG. 24(A) is a perspective view of a battery pack showing one embodiment of the present invention, FIG. 24(B) is a block diagram of the battery pack, and FIG. 24(C) is a block diagram of a vehicle having a motor. [Diagram 25] 25(A) to (D) are diagrams illustrating an example of a transportation vehicle. [Figure 26] 26A and 26B are diagrams illustrating a power storage device of one embodiment of the present invention. [Figure 27] FIG. 27(A) is a diagram showing an electric bicycle, FIG. 27(B) is a diagram showing a secondary battery of the electric bicycle, and FIG. 27(C) is a diagram explaining an electric motorcycle. [Figure 28] 28A to 28D are diagrams illustrating examples of electronic devices. [Figure 29] FIG. 29(A) shows an example of a wearable device, FIG. 29(B) shows a perspective view of a wristwatch type device, and FIG. 29(C) is a diagram illustrating a side view of the wristwatch type device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0039] Hereinafter, the embodiments of the present invention will be described in detail with reference to the drawings. However, the present invention is not limited to the following description, and it will be easily understood by those skilled in the art that the form and details of the present invention can be modified in various ways. Furthermore, the present invention is not to be interpreted as being limited to the description of the embodiments shown below.
[0040] In this specification and elsewhere, Miller indices are used to indicate crystal planes and directions. Individual planes indicating crystal planes are expressed in parentheses. In crystallography, crystal planes, directions, and space groups are indicated by placing a superscript bar on the numbers, but in this specification and elsewhere, due to restrictions on notation in the application, the numbers may be expressed by placing a - (minus sign) before them instead of placing a bar above them.
[0041] In this specification and the like, segregation refers to a phenomenon in which a certain element (eg, B) is spatially non-uniformly distributed in a solid composed of a plurality of elements (eg, A, B, C).
[0042] In this specification, homogeneity refers to a phenomenon in which a certain element (e.g., A) is distributed with similar characteristics in a specific region in a solid consisting of multiple elements (e.g., A, B, C). The concentration of the element in each specific region may be substantially the same. For example, the difference in element concentration between each specific region may be within 10%. Examples of specific regions include the surface, convex portions, concave portions, and internal regions.
[0043] In this specification, the region from the surface of the positive electrode active material to about 10 nm is called the near-surface region (or surface layer). Surfaces caused by cracks or cracks may also be called the surface. The region deeper than the near-surface region of the positive electrode active material is called the inner region (or inner). Of the near-surface region of the positive electrode active material, the region from the surface to 3 nm is called the outermost surface layer. The surface of the positive electrode active material refers to the surface of the complex oxide including the near-surface region and the inner region including the outermost surface layer. Therefore, the positive electrode active material does not include carbonic acid, hydroxyl groups, etc. that are chemically adsorbed after preparation. Also, it does not include electrolytes, binders, conductive materials, or compounds derived from these that are attached to the positive electrode active material. Also, the positive electrode active material does not necessarily have to be a region having lithium sites that contribute to charging and discharging.
[0044] In the present specification, the layered rock-salt type crystal structure of a composite oxide containing lithium and a transition metal refers to a crystal structure having a rock-salt type ion arrangement in which cations and anions are alternately arranged, and in which the transition metal and lithium are regularly arranged to form a two-dimensional plane, allowing two-dimensional diffusion of lithium. Note that some defects such as deficiencies of cations or anions may be present, as long as two-dimensional diffusion of lithium ions is possible. Strictly speaking, the layered rock-salt type crystal structure may have a structure in which the lattice of the rock-salt type crystal is distorted.
[0045] In this specification and the like, the rock salt type crystal structure refers to a structure in which cations and anions are arranged alternately, and some cations or anions may be missing.
[0046] In the present specification and the like, the pseudo-spinel crystal structure of a composite oxide containing lithium and a transition metal refers to a crystal structure that is in the space group R-3m and is not a spinel crystal structure, but has ions of cobalt, magnesium, etc. occupying 6-coordination oxygen positions and has a symmetry similar to that of the spinel type in the arrangement of cations. In the pseudo-spinel crystal structure, a light element such as lithium may occupy 4-coordination oxygen positions, and in this case, the arrangement of ions also has a symmetry similar to that of the spinel type.
[0047] It can also be said that the pseudo-spinel type crystal structure is a crystal structure similar to the CdCl2 type crystal structure, although it has a certain probability of having Li between the layers. This CdCl2 type-like crystal structure was observed when lithium nickel oxide was charged to a charge depth of 0.94 (Li 0.06 The crystal structure is close to that of lithium cobalt oxide (NiO2), but it is known that pure lithium cobalt oxide or layered rock salt type positive electrode active materials that contain a large amount of cobalt do not usually have this crystal structure.
[0048] The layered rock salt crystal and the anions of the rock salt crystal have a cubic close-packed structure (face-centered cubic lattice structure). It is presumed that the anions of the pseudo-spinel crystal also have a cubic close-packed structure. When they contact, there is a crystal plane where the orientation of the cubic close-packed structure formed by the anions is aligned. However, the space group of the layered rock salt crystal and the pseudo-spinel crystal is R-3m, which is different from the space group Fm-3m (the space group of a general rock salt crystal) and Fd-3m (the space group of a rock salt crystal with the simplest symmetry) of the rock salt crystal, so the Miller indices of the crystal planes that satisfy the above conditions are different between the layered rock salt crystal and the pseudo-spinel crystal and the rock salt crystal. In this specification, when the orientation of the cubic close-packed structure formed by the anions is aligned in the layered rock salt crystal, the pseudo-spinel crystal, and the rock salt crystal, it may be said that the crystal orientation is approximately the same.
[0049] The crystal orientation of the two regions roughly coincides with each other, which can be determined from TEM (transmission electron microscope) images, STEM (scanning transmission electron microscope) images, HAADF-STEM (high-angle annular dark-field scanning transmission electron microscope) images, ABF-STEM (annular bright-field scanning transmission electron microscope) images, etc. X-ray diffraction (XRD), electron beam diffraction, neutron beam diffraction, etc. can also be used for the determination. In TEM images, etc., the arrangement of cations and anions can be observed as repeated bright and dark lines. When the orientation of the cubic close-packed structure in the layered rock salt type crystal and the rock salt type crystal is aligned, it can be observed that the angle between the repeated bright and dark lines between the crystals is 5 degrees or less, more preferably 2.5 degrees or less. In TEM images, etc., light elements such as oxygen and fluorine may not be clearly observed, but in such cases, the agreement of the orientation can be determined from the arrangement of metal elements.
[0050] In this specification and the like, a mixture refers to a mixture of multiple materials. A mixture in which elements in the mixture have undergone mutual diffusion may be called a composite. A mixture that contains some unreacted materials may also be called a composite.
[0051] In this specification, the theoretical capacity of a positive electrode active material refers to the amount of electricity when all of the lithium that can be inserted and removed from the positive electrode active material is removed. For example, the theoretical capacity of LiCoO2 is 274 mAh / g, the theoretical capacity of LiNiO2 is 274 mAh / g, and the theoretical capacity of LiMn2O4 is 148 mAh / g.
[0052] In this specification and the like, the depth of charge when all intercalable and deintercalable lithium is intercalated is defined as 0, and the depth of charge when all intercalable and deintercalable lithium contained in the positive electrode active material is deintercalated is defined as 1.
[0053] In this specification, charging refers to moving lithium ions from the positive electrode to the negative electrode in a battery and moving electrons from the negative electrode to the positive electrode in an external circuit. For a positive electrode active material, charging refers to removing lithium ions.
[0054] Generally, in positive electrode active materials that have a layered rock-salt crystal structure, when the lithium between the layered structure consisting of transition metals and oxygen decreases, the crystal structure becomes unstable. Therefore, in secondary batteries that use general lithium cobalt oxide, charging is limited to a charge depth of 0.4, a charging voltage of 4.3V (in the case of lithium counter electrode), and a charging capacity of about 160mAh / g.
[0055] In contrast, a positive electrode active material with a charge depth of 0.74 to 0.9, more specifically, a charge depth of 0.8 to 0.83, is referred to as a positive electrode active material charged at a high voltage. For example, if LiCoO2 is charged to a charge capacity of 219.2mAh / g, it is a positive electrode active material charged at a high voltage. In addition, in the case of LiCoO2, a positive electrode active material is charged at a constant current with a charge voltage of 4.525V to 4.65V (in the case of lithium counter electrode) in a 25°C environment, and then charged at a constant voltage until the current value becomes 0.01C or about 1 / 5 to 1 / 100 of the current value during constant current charging, and is also referred to as a positive electrode active material charged at a high voltage. Note that C is an abbreviation for Capacity rate, and 1C refers to the magnitude of the current that completely charges or completely discharges the charge / discharge capacity of a secondary battery in one hour.
[0056] Similarly, discharging refers to moving lithium ions from the negative electrode to the positive electrode in the battery and moving electrons from the positive electrode to the negative electrode in the external circuit. For positive electrode active materials, discharging refers to inserting lithium ions. A positive electrode active material with a charge depth of 0.06 or less, or a positive electrode active material that has been discharged from a state charged at a high voltage to 90% or more of its charge capacity, is considered to be a fully discharged positive electrode active material. For example, in LiCoO2, if the charge capacity is 219.2mAh / g, it is in a state charged at a high voltage, and a positive electrode active material after discharging 197.3mAh / g or more, which is 90% of the charge capacity, from this state is considered to be a fully discharged positive electrode active material. In addition, in LiCoO2, a positive electrode active material after constant current discharge until the battery voltage becomes 3V or less (in the case of lithium counter electrode) in a 25°C environment is also considered to be a fully discharged positive electrode active material.
[0057] In addition, in the present specification and the like, an example of a secondary battery using a positive electrode and a positive electrode active material of one embodiment of the present invention may be shown in which a lithium metal is used as a counter electrode, but the secondary battery of one embodiment of the present invention is not limited thereto. Other materials, for example, graphite, lithium titanate, and the like may be used as a negative electrode. The properties of the positive electrode and the positive electrode active material of one embodiment of the present invention, such as the crystal structure being unlikely to be broken even after repeated charging and discharging, and good cycle characteristics being obtained, are not affected by the material of the negative electrode. In addition, in the secondary battery of one embodiment of the present invention, an example of charging and discharging at a voltage higher than a general charging voltage of about 4.6 V with a lithium counter electrode may be shown, but charging and discharging at a lower voltage may be performed. When charging and discharging at a lower voltage, the cycle characteristics are expected to be improved more than those shown in the present specification and the like.
[0058] (Embodiment 1) In this embodiment, a positive electrode active material of one embodiment of the present invention will be described with reference to FIGS.
[0059] FIG. 1(A) is a cross-sectional view of a positive electrode active material 100 according to one embodiment of the present invention. FIGS. 2(A), (B1), and (B2) are enlarged views of the vicinity of AB in FIG. 1(A). FIGS. 3(A1), (A2), (B1), (B2), (C1), and (C2) are enlarged views of the vicinity of CD in FIG. 1(A). FIG. 1(B) is a cross-sectional view of a positive electrode active material 104 according to another embodiment of the present invention, and FIG. 1(C) is a cross-sectional view of a positive electrode active material 105 according to another embodiment of the present invention, the details of which will be described in Embodiment 2.
[0060] As shown in FIG. 1(A), FIG. 2(A), (B1) and (B2), the positive electrode active material 100 has a surface near region 100a and an inner region 100b. In these figures, the boundary between the surface near region 100a and the inner region 100b is indicated by a dashed line. The surface near region 100a can also be called the first region, and the inner region 100b can also be called the second region. It can also be said that the positive electrode active material 100 has a first region near the surface and a second region that contacts a part of the first region. Also, FIG. 1(A) indicates a part of the crystal grain boundary 101 by a dashed line. Also, FIG. 2(A) indicates the boundary of the outermost surface layer 100c in the surface near region 100a by a dashed line.
[0061] <Each region and lattice constant> In the positive electrode active material 100 according to one embodiment of the present invention, both the surface near region 100a and the inner region 100b preferably have a crystal structure. In addition, the lattice constant A of the a-axis of the crystal structure of the surface near region 100a is smaller than the lattice constant A of the a-axis of the crystal structure of the inner region 100b. core It is preferable that the lattice constant of the b-axis of the crystal structure of the surface near region 100a is larger than the lattice constant B core In addition, the lattice constant of the c-axis of the crystal structure in the surface near region 100a is preferably larger than the lattice constant C core It is preferable that it is greater than .
[0062] Furthermore, it is preferable that the outermost surface layer 100c of the positive electrode active material 100 also has a crystalline structure. surface The lattice constant A of the a-axis of the surface near region 100a and the lattice constant A of the a-axis of the internal region 100b are core In addition, the lattice constant B surface The lattice constant B of the b-axis of the surface near region 100a and the lattice constant B of the b-axis of the internal region 100b are core The c-axis lattice constant C surface The c-axis lattice constant of the surface near region 100a and the c-axis lattice constant C core It is preferable that it is greater than .
[0063] The lattice constant A of the a-axis of the outermost layer surface From the above, the lattice constant A of the a-axis in the inner region core The difference minus Δ A Similarly, the c-axis lattice constant of the outermost layer, C surface From the above, the lattice constant C of the c-axis in the inner region core The difference minus Δ C In this case, Δ A Δ C It is preferable that is large.
[0064] In order to make it easier to compare the lattice constants between regions, the same crystal structure is used as a model for all regions to calculate the lattice constants. For example, if the lattice constants of the surface-nearby region 100a, the inner region 100b, and the outermost surface layer 100c are calculated using a layered rock-salt type crystal structure as a model, it becomes easier to compare the lattice constants of each region. In the layered rock-salt type crystal structure, the lengths of the a-axis and the b-axis are equal, so in the following, the a-axis will be described as a representative for the layered rock-salt type.
[0065] Hereinafter, an example will be described in which a layered rock-salt type crystal structure is used as a model for calculating the lattice constant of each region, but this is not limiting. It is preferable to select an optimal structure depending on the material of the positive electrode active material 100. For example, it is preferable to adopt a crystal structure that occupies the largest volume among the crystal structures possessed by the positive electrode active material 100. In addition to the layered rock-salt type, for example, a rock-salt type, a spinel type, an olivine type, or other crystal structure can be used.
[0066] The determination of whether the near-surface region 100a, the internal region 100b, and the outermost surface layer 100c have a crystalline structure, and the determination of the lattice constant if they do, can be performed, for example, by cross-sectional TEM, cross-sectional STEM, and electron diffraction including selected area electron diffraction and ultrafine electron diffraction.
[0067] If a regular arrangement of cations and anions can be observed in a cross-sectional TEM image, cross-sectional STEM image, etc., it can be said to have a crystalline structure. Also, if a diffraction pattern with regular spots can be observed in an electron diffraction image, etc., it can be said to have a crystalline structure.
[0068] Selected area electron diffraction allows analysis of crystal structure in a small area of about 20 nm, and ultrafine electron diffraction allows analysis of an even smaller area of about 1 nm, and is suitable for determining the lattice constants of the surface near region 100a and the outermost surface layer 100c.
[0069] However, these electron diffraction methods may cause measurement errors due to distortion of the camera length, etc. Therefore, it is preferable that the significant figures of the lattice constant obtained by the electron diffraction method are two digits. Alternatively, the lattice constant obtained by the electron diffraction method may be corrected by referring to the lattice constant obtained by powder XRD, literature values, etc.
[0070] For example, the inner region 100b occupies most of the volume of the positive electrode active material 100. Therefore, the lattice constant of the entire positive electrode active material 100 determined by powder XRD can be considered to be equal to the lattice constant of the inner region 100b determined by electron diffraction. Therefore, the corrected lattice constant of the surface near region 100a can be obtained from the ratio of the lattice constants of the inner region 100b and the surface near region 100a obtained by electron diffraction and the lattice constant obtained by powder XRD.
[0071] The surface near region 100a preferably has a higher concentration of an additive element, which will be described later, than the inner region 100b. The additive preferably has a concentration gradient. When there are multiple additive elements, it is preferable that the depth of the concentration peak from the surface differs depending on the additive element.
[0072] For example, it is preferable that a certain additive element X has a concentration gradient that increases from the inner region 100b toward the surface, as shown by the gradation in Fig. 2 (B1). Examples of additive elements X that preferably have such a concentration gradient include magnesium, fluorine, titanium, silicon, phosphorus, boron, and calcium.
[0073] As shown by the gradation in FIG. 2(B2), the additional element Y preferably has a concentration gradient and a concentration peak in a region deeper than that in FIG. 2(B1). The concentration peak may be in the surface vicinity region or may be deeper than the surface vicinity region. It is preferable that the concentration peak is in a region other than the outermost surface layer. For example, it is preferable that the peak is in a region from 5 nm to 30 nm from the surface. Examples of the additional element Y that preferably has such a concentration gradient include aluminum and manganese.
[0074] Moreover, due to the above-mentioned concentration gradient of the added element, it is preferable that the crystal structure changes continuously from the inner region 100b toward the surface-nearby region 100a and the outermost surface layer 100c.
[0075] For example, a case where the inner region 100b has a layered rock-salt type crystal structure will be described. One of the characteristics of the layered rock-salt type crystal structure is that it has transition metal site layers and lithium site layers alternately between cubic close-packed structures of anions. Therefore, in a cross-sectional TEM or the like, the inner region 100b is observed to have transition metal site layers with large atomic numbers observed with strong brightness and lithium site layers observed with weak brightness alternately. Note that the anions oxygen and fluorine both have small atomic numbers and are observed with the same brightness as lithium. Note that these elements with small atomic numbers do not appear as clear bright spots, and may only have a slight difference in brightness from the background.
[0076] In this specification, when a material has alternating layers observed with strong brightness and layers observed with weak brightness in a cross-sectional TEM image or the like, it is said to have the characteristics of a layered rock-salt type crystal structure.
[0077] On the other hand, since the concentration of the additive element is high in the outermost surface layer 100c, the additive element enters part of the lithium site layer. Since the lithium site is surrounded by anions such as oxygen, metallic elements such as magnesium and aluminum are likely to enter the lithium site. In addition, transition metals such as cobalt may enter part of the lithium site layer. Since all of these metals have a higher atomic number than lithium, they are observed with a higher brightness than lithium in cross-sectional TEM, etc.
[0078] In some cases, the transition metal layer contains an additive element or lithium. In such cases, it is observed with a weaker brightness than the transition metal in cross-sectional TEM.
[0079] When a large amount of cation replacement occurs in this way, the battery has the characteristics of a rock-salt type crystal structure in which there is no difference between the lithium site and the transition metal site. The presence of the characteristics of a rock-salt type crystal structure can be said to suggest that the additive element is present in a sufficient concentration. If the additive element is present in a sufficient concentration, the elution of the transition metal that may occur during charging at a high voltage can be suppressed. This improves the battery characteristics, especially the durability to continuous charging, and makes it possible to produce a secondary battery that is safe and reliable.
[0080] On the other hand, it is preferable that the outermost surface layer 100c also has the same characteristics of a layered rock-salt type crystal structure as the inner region 100b. If the surface is covered only with a rock-salt type crystal structure, the lithium diffusion path may be blocked, and the internal resistance may increase during charging and discharging. For the same reason, it is preferable that the characteristics of the rock-salt type crystal structure are limited to about 3 nm from the surface.
[0081] Therefore, it is preferable that the outermost layer 100c has both the characteristics of a layered rock-salt type crystal structure and the characteristics of a rock-salt type crystal structure, i.e., the outermost layer 100c has a layered rock-salt type crystal structure having alternating layers observed with high brightness and layers observed with low brightness in a cross-sectional TEM image, etc., and further has a metal with an atomic number larger than that of lithium in some of the lithium sites.
[0082] When the additive element is present at a preferred concentration in a portion of the lithium sites of the outermost layer 100c, the brightness of the lithium site layer in a cross-sectional TEM image is 3% to 60% of the brightness of the transition metal site layer. More preferably, it is 4% to 50%. Even more preferably, it is 6% to 40%. Alternatively, 3% to 50% is preferred. Alternatively, 3% to 40% is preferred. Alternatively, 4% to 60% is preferred. Alternatively, 4% to 40% is preferred. Alternatively, 6% to 60% is preferred. Alternatively, 6% to 50% is preferred. The lithium site layer and transition metal site layer used for comparison preferably have a width of 5 nm or more.
[0083] The brightness in cross-sectional TEM, etc., can be calculated, for example, by integrating the brightness of pixels in a cross-sectional TEM dark-field image. Similarly, the brightness of the transition metal site layer and the lithium site layer can be calculated by integrating the brightness of pixels parallel to these layers. Specifically, the image can be made grayscale, with black being brightness 0 and white being brightness 255, and the brightness of each pixel can be integrated column by column. In addition, to make it easier to compare the brightness of the metal site layer, correction can be made to remove the brightness derived from elements with small atomic numbers, such as oxygen.
[0084] The sample for cross-sectional TEM has a thickness of about 20 nm to 200 nm. Therefore, if the surface of the positive electrode active material 100 is uneven, accurate brightness may not be obtained in a shallow area from the surface. Therefore, when comparing brightness, it is necessary to compare the brightness between areas where brightness can be obtained stably. For example, when the maximum brightness of the transition metal site layer is 1, a transition metal site layer having a brightness of 0.7 or more is considered to have a stable brightness.
[0085] In this specification and the like, the surface of the positive electrode active material 100 in a cross-sectional TEM image, a cross-sectional STEM image, etc. refers to the surface where a metal element is first observed. More specifically, it refers to the point where the atomic nucleus of the metal element, that is, the point where the brightness peak exists in the cross-sectional TEM image and the like.
[0086] It is sufficient that at least a part of the outermost layer of the positive electrode active material has both the characteristics of the layered rock salt type crystal structure and the characteristics of the rock salt type crystal structure as described above. If the crystal plane exposed on the surface of the positive electrode active material is approximately parallel to the (001) plane, the above characteristics are easy to observe, but depending on the crystal plane, these characteristics may not be clearly observed. Therefore, the brightness ratio between the transition metal site layer and the lithium site layer does not necessarily have to be within the above range.
[0087] The characteristics of the layered rock salt type crystal structure and the rock salt type crystal structure can also be analyzed by electron diffraction.
[0088] The rock-salt type has a high degree of symmetry because it has only one type of cation. On the other hand, the layered rock-salt type has a lower degree of symmetry because it has two types of cations arranged in a regular pattern. As a result, there are twice as many bright spots corresponding to specific plane orientations as there are in the rock-salt type.
[0089] In the case of a crystal structure that has characteristics of both the rock salt type and the layered rock salt type, the diffraction pattern shows that there exists a plane orientation in which bright spots of high brightness and bright spots of low brightness are arranged alternately. Bright spots common to the rock salt type and the layered rock salt type have high brightness, while bright spots that occur only in the layered rock salt type have low brightness.
[0090] It is preferable that the transition metals, particularly cobalt and nickel, are uniformly dissolved in the entire positive electrode active material 100. When the concentration of some transition metals, for example nickel, is low, it may be below the detection limit in analysis such as XPS or XPS.
[0091] For example, if the number of nickel atoms is 2% or less compared to the number of cobalt atoms, the nickel content in the lithium composite oxide will be 0.5 atomic % or less. On the other hand, the detection limit of XPS and EDX is generally about 1 atomic %. In this case, if nickel is uniformly dissolved in solid solution throughout the positive electrode active material 100, it may be below the detection limit by analytical methods such as XPS and EDX. In this case, being below the detection limit may suggest that the nickel concentration is 1 atomic % or less and that nickel is dissolved in solid solution throughout the positive electrode active material 100.
[0092] On the other hand, by using ICP-MS or other methods, it is possible to quantify transition metals even at concentrations of 1 atomic % or less.
[0093] The positive electrode active material 100 may have an additive element that is widely dissolved in the internal region 100b and does not have a concentration gradient. Also, a part of the transition metal M contained in the positive electrode active material 100, such as manganese, may have a concentration gradient that increases from the internal region 100b toward the surface.
[0094] <Contained elements> The positive electrode active material 100 contains lithium, a transition metal M, oxygen, and an additive. The positive electrode active material 100 may be said to be a composite oxide represented by LiMO2 to which the additive has been added. However, the positive electrode active material of one embodiment of the present invention only needs to have the crystal structure of a lithium composite oxide represented by LiMO2, and the composition is not strictly limited to Li:M:O=1:1:2.
[0095] As the transition metal M of the positive electrode active material 100, it is preferable to use a metal that can form a layered rock salt type composite oxide belonging to the space group R-3m together with lithium. For example, at least one of manganese, cobalt, and nickel can be used. That is, as the transition metal of the positive electrode active material 100, only cobalt may be used, only nickel may be used, two types of cobalt and manganese, or two types of cobalt and nickel may be used, or three types of cobalt, manganese, and nickel may be used. That is, the positive electrode active material 100 can have a composite oxide containing lithium and a transition metal M, such as lithium cobalt oxide, lithium nickel oxide, lithium cobalt oxide in which a part of cobalt is replaced with manganese, lithium cobalt oxide in which a part of cobalt is replaced with nickel, and nickel-manganese-lithium cobalt oxide. When nickel is used as the transition metal M in addition to cobalt, the deviation of the layered structure consisting of an octahedron of cobalt and oxygen may be suppressed. Therefore, the crystal structure may become more stable, particularly in a charged state at a high temperature, which is preferable.
[0096] As the additive element of the positive electrode active material 100, it is preferable to use at least one of magnesium, fluorine, aluminum, titanium, zirconium, vanadium, iron, chromium, niobium, cobalt, arsenic, zinc, silicon, sulfur, phosphorus, and boron. These elements may further stabilize the crystal structure of the positive electrode active material 100, as described later. That is, the positive electrode active material 100 can have lithium cobalt oxide to which magnesium and fluorine are added, lithium cobalt oxide to which magnesium, fluorine, and titanium are added, lithium nickel-cobalt oxide to which magnesium and fluorine are added, lithium cobalt-aluminate to which magnesium and fluorine are added, lithium nickel-cobalt-aluminate, lithium nickel-cobalt-aluminate to which magnesium and fluorine are added, lithium nickel-manganese-cobalt oxide to which magnesium and fluorine are added, and the like. In this specification and the like, the term "additive element" may be replaced with "mixture," "part of raw material," "impurity," and the like.
[0097] In the positive electrode active material 100 of one embodiment of the present invention, even if lithium is released from the positive electrode active material 100 upon charging, the surface-nearby region 100a where the concentration of the additive 100 is high, i.e., the outer periphery of the particle, reinforces the layered structure consisting of cobalt and oxygen octahedra so as not to be destroyed.
[0098] In addition, it is preferable that the concentration gradient of the additive is uniformly present in the surface vicinity region 100a of the positive electrode active material 100. Even if a part of the surface vicinity region 100a is reinforced, if there is a part without reinforcement, stress may be concentrated in the unreinforced part. If stress is concentrated in a part of the particle, defects such as cracks may occur there, which may lead to cracking of the positive electrode active material and a decrease in charge / discharge capacity.
[0099] However, the concentration gradient of all kinds of additive elements does not necessarily have to be uniform in the entire surface near region 100a of the positive electrode active material 100. Examples of the distribution of additive element X near the CD in Fig. 1(A) are shown in Figs. 3(A1), (B1), and (C1). Examples of the distribution of additive element Y near the CD are shown in Figs. 3(A2), (B2), and (C2).
[0100] For example, as shown in Figures 3(A1) and (A2), there may be regions where the additive element X and the additive element Y are not present. Also, as shown in Figures 3(B1) and (B2), there may be regions where the additive element X is present but the additive element Y is not present. Also, as shown in Figures 3(C1) and (C2), there may be regions where the additive element X is not present but the additive element Y is present. It is preferable that the additive element Y in Figure 3(C2) has a peak in a region that is not the outermost surface layer, as in Figure 2(B2). For example, it is preferable that the peak is in a region from 3 nm to 30 nm from the surface.
[0101] The positive electrode active material 100 may have an electric field relaxation region 103 as shown in FIG. 1(A). As an additive element for forming the electric field relaxation region 103, it is preferable to use at least one of Hf, Zr, Y, Ba, Ti, Pb, Sc, Sr, Bi, and Ta. In this specification, the electric field relaxation region 103 is considered to be a part of the positive electrode active material 100, regardless of whether it contributes to charging and discharging. The additive element may be present in the electric field relaxation region 103 at a higher concentration than in the inner region 100b or the surface vicinity region 100a.
[0102] The positive electrode active material 100 may have recesses, cracks, dents, V-shaped cross sections, etc. These are defects, and repeated charging and discharging may cause the elution of transition metals, the collapse of the crystal structure, cracks in the body, etc. Although not shown, when the electric field relaxation region 103 is formed so as to cover the recesses, cracks, dents, V-shaped cross sections, etc., the deterioration caused by these defects can be suppressed, and the positive electrode active material 100 can have excellent reliability and cycle characteristics.
[0103] The positive electrode active material 100 may contain an additive element and may have an electric field relaxation region 103 as a region in which a material containing the additive element and capable of having ferroelectricity is concentrated. Examples of the material capable of having ferroelectricity include hafnium oxide, zirconium oxide, HfZrO X (X>0), yttria-stabilized zirconia (YSZ), barium titanate, PbTiO XExamples of such materials include lead zirconate titanate (PZT), barium strontium titanate (BST), strontium titanate, and strontium bismuthate tantalate. For example, the crystal structure (characteristics) of hafnium oxide may change depending on not only the film formation conditions but also the film configurations above and below it and the process, so in this specification, ferroelectrics are not used to refer to only materials that exhibit ferroelectricity, but rather to materials that can have ferroelectricity or that are made to have ferroelectricity.
[0104] When the positive electrode active material 100 has the electric field relaxation region 103, the electric field relaxation region is formed between the positive electrode active material 100 and the electrolyte, thereby making it possible to realize a secondary battery that is electrochemically stable at high potential.
[0105] In this specification and the like, uneven distribution refers to the concentration of a certain element being different from that of other elements, and may also be referred to as segregation, precipitation, non-uniformity, bias, high concentration, and the like.
[0106] Magnesium, which is one of the additive elements X, is divalent and is more stable at the lithium site than at the transition metal site in the layered rock-salt crystal structure, and therefore is more likely to enter the lithium site. The presence of magnesium at an appropriate concentration at the lithium site in the surface-nearby region 100a makes it easier to maintain the layered rock-salt crystal structure. At an appropriate concentration, magnesium is preferable because it does not adversely affect the insertion and extraction of lithium during charging and discharging.
[0107] Aluminum, one of the additive elements Y, is trivalent and has a strong bond with oxygen. Therefore, when aluminum is added as an additive, the change in the crystal structure when it enters the lithium site can be suppressed. Therefore, it is possible to obtain a positive electrode active material 100 whose crystal structure is not easily destroyed even when the charge and discharge are repeated.
[0108] Titanium oxide is known to have superhydrophilicity. Therefore, by forming the cathode active material 100 having titanium oxide in the surface vicinity region 100a, it is possible that the wettability with a highly polar solvent is improved. When the cathode active material 100 is formed into a secondary battery, the contact at the interface between the cathode active material 100 and a highly polar electrolyte is improved, and it is possible that an increase in internal resistance can be suppressed.
[0109] As the charging voltage of a secondary battery increases, the voltage of the positive electrode generally increases. The positive electrode active material of one embodiment of the present invention has a stable crystal structure even at high voltages. Since the crystal structure of the positive electrode active material is stable in a charged state, it is possible to suppress a decrease in charge / discharge capacity due to repeated charging and discharging.
[0110] Moreover, a short circuit in a secondary battery not only causes problems in the charging and discharging operations of the secondary battery, but may also lead to heat generation and fire. In order to realize a safe secondary battery, it is preferable that a short circuit current is suppressed even at a high charging voltage. The positive electrode active material 100 of one embodiment of the present invention suppresses a short circuit current even at a high charging voltage. Therefore, a secondary battery that achieves both high charging and discharging capacity and safety can be obtained.
[0111] A secondary battery using the positive electrode active material 100 of one embodiment of the present invention preferably simultaneously satisfies high charge / discharge capacity, excellent charge / discharge cycle characteristics, and safety.
[0112] The concentration gradient of the additive can be evaluated, for example, by using energy dispersive X-ray spectroscopy (EDX), electron probe microanalysis (EPMA), etc. Among EDX measurements, the measurement while scanning an area and evaluating the area two-dimensionally may be called EDX area analysis. In addition, the extraction of data of a linear area from EDX area analysis and the evaluation of the distribution of atomic concentration within the positive electrode active material particle may be called line analysis.
[0113] By EDX surface analysis (e.g., element mapping), the concentration of the additive can be quantitatively analyzed in the surface near region 100a including the outermost surface layer 100c of the positive electrode active material 100, the inner region 100b, and the vicinity of the grain boundaries 101, etc. Furthermore, by EDX line analysis, the peak of the concentration of the additive can be analyzed. Furthermore, by electron energy loss spectroscopy (EELS), the element composition and chemical bond state can be quantitatively analyzed in the surface near region 100a including the outermost surface layer 100c of the positive electrode active material 100, the inner region 100b, and the vicinity of the grain boundaries 101, etc.
[0114] When EDX line analysis is performed on the positive electrode active material 100, the peak of the magnesium concentration in the surface near region 100a is preferably present at a depth of up to 3 nm from the surface toward the center of the positive electrode active material 100, that is, in the outermost surface layer 100c, more preferably at a depth of up to 1 nm, and even more preferably at a depth of up to 0.5 nm.
[0115] In addition, the distribution of fluorine in the positive electrode active material 100 preferably overlaps with the distribution of magnesium. Therefore, when EDX analysis is performed, the peak of the fluorine concentration in the surface near region 100a is preferably present at a depth of 3 nm from the surface of the positive electrode active material 100 toward the center, that is, at the outermost surface layer 100c, more preferably at a depth of 1 nm, and even more preferably at a depth of 0.5 nm.
[0116] It is not necessary that all additives have the same concentration distribution. For example, when the positive electrode active material 100 has aluminum as an additive, it is preferable that the distribution is slightly different from that of magnesium and fluorine. For example, when EDX ray analysis is performed, it is preferable that the magnesium concentration peak is closer to the surface than the aluminum concentration peak in the surface vicinity region 100a. For example, the aluminum concentration peak is preferably present at a depth of 0.5 nm to 50 nm from the surface toward the center of the positive electrode active material 100, and more preferably at a depth of 5 nm to 30 nm. Alternatively, it is preferable that it is present at a depth of 0.5 nm to 30 nm. Alternatively, it is preferable that it is present at a depth of 5 nm to 50 nm.
[0117] The surface of the positive electrode active material 100 in the EDX line analysis can be estimated, for example, as follows: The point where the amount of an element uniformly present in the internal region 100b of the positive electrode active material 100, for example, oxygen or a transition metal such as cobalt, becomes half of the amount detected in the internal region is defined as the surface.
[0118] Since the positive electrode active material 100 is a composite oxide, it is preferable to estimate the surface using the amount of detected oxygen. Specifically, first, the average oxygen concentration O ave In this case, oxygen O that is thought to be chemically adsorbed or background outside the surface is calculated. background If O is detected, the measurement background The average oxygen concentration is calculated by subtracting ave This average value O ave That is, 1 / 2O ave The measurement point showing the measurement value closest to the above can be estimated to be the surface of the positive electrode active material.
[0119] Therefore, the surface can also be estimated using the transition metal contained in the positive electrode active material 100. For example, when 95% or more of the transition metal is cobalt, the surface can be estimated in the same manner as above using the detected amount of cobalt. Alternatively, the surface can be estimated in the same manner using the sum of the detected amounts of a plurality of transition metals. The detected amount of the transition metal is less susceptible to the influence of chemical adsorption, and is therefore suitable for estimating the surface.
[0120] Furthermore, when the positive electrode active material 100 is subjected to a line analysis or an area analysis, the ratio (I / M) of the additive I to the transition metal M in the vicinity of the crystal grain boundary 101 is preferably 0.020 or more and 0.50 or less. More preferably, it is 0.025 or more and 0.30 or less. Still more preferably, it is 0.030 or more and 0.20 or less. Or it is preferably 020 or more and 0.30 or less. Or it is preferably 020 or more and 0.20 or less. Or it is preferably 025 or more and 0.50 or less. Or it is preferably 025 or more and 0.20 or less. Or it is preferably 0.030 or more and 0.50 or less. Or it is preferably 0.030 or more and 0.30 or less.
[0121] For example, when the additive is magnesium and the transition metal is cobalt, the ratio of the number of magnesium atoms to cobalt atoms (Mg / Co) is preferably 0.020 or more and 0.50 or less. More preferably, it is 0.025 or more and 0.30 or less. Even more preferably, it is 0.030 or more and 0.20 or less. Or it is preferably 020 or more and 0.30 or less. Or it is preferably 020 or more and 0.20 or less. Or it is preferably 025 or more and 0.50 or less. Or it is preferably 025 or more and 0.20 or less. Or it is preferably 0.030 or more and 0.50 or less. Or it is preferably 0.030 or more and 0.30 or less.
[0122] <Crystal structure>
[0123] Materials with a layered rock-salt crystal structure, such as lithium cobalt oxide (LiCoO2), are known to have high discharge capacity and are excellent as positive electrode active materials for secondary batteries.
[0124] It is known that the strength of the Jahn-Teller effect in transition metal compounds varies depending on the number of electrons in the d orbital of the transition metal.
[0125] In compounds containing nickel, distortion may occur easily due to the Jahn-Teller effect. Therefore, when LiNiO2 is charged and discharged at high voltage, there is a concern that the crystal structure may collapse due to distortion. It is suggested that the influence of the Jahn-Teller effect is small in LiCoO2, and it may have better resistance when charged at high voltage, which is preferable.
[0126] The positive electrode active material will be described with reference to Fig. 9 to Fig. 12. In Fig. 9 to Fig. 12, the case where cobalt is used as the transition metal M contained in the positive electrode active material will be described.
[0127] <Conventional positive electrode active materials> The positive electrode active material shown in Fig. 11 is lithium cobalt oxide (LiCoO2) to which fluorine and magnesium are not added by the manufacturing method described later. As described in Non-Patent Documents 1 and 2, etc., the crystal structure of the lithium cobalt oxide shown in Fig. 11 changes depending on the charge depth.
[0128] As shown in Figure 11, lithium cobalt oxide at a charge depth of 0 (discharged state) has a region with a crystal structure of space group R-3m, and there are three CoO2 layers in the unit cell. Therefore, this crystal structure is sometimes called an O3 type crystal structure. Note that a CoO2 layer is an octahedral structure in which cobalt is coordinated with six oxygen atoms, and the octahedral structure is continuous on a plane with edge sharing.
[0129] At a charge depth of 1, the crystal structure has the space group P-3m1, and there is one CoO2 layer in the unit cell. Therefore, this crystal structure is sometimes called the O1 type crystal structure.
[0130] Lithium cobalt oxide at a charge depth of about 0.88 has a crystal structure of space group R-3m. This structure can be said to be a structure in which a CoO2 structure such as P-3m1(O1) and a LiCoO2 structure such as R-3m(O3) are alternately stacked. Therefore, this crystal structure is sometimes called an H1-3 type crystal structure. In reality, the number of cobalt atoms per unit cell in the H1-3 type crystal structure is twice that of other structures. However, in this specification, including FIG. 11, the c-axis of the H1-3 type crystal structure is shown as half the unit cell in order to make it easier to compare with other structures.
[0131] As an example, as described in Non-Patent Document 3, the coordinates of cobalt and oxygen in the unit cell of the H1-3 type crystal structure can be expressed as Co(0,0,0.42150±0.00016), O1(0,0,0.27671±0.00045), and O2(0,0,0.11535±0.00045). O1 and O2 are oxygen atoms. Thus, the H1-3 type crystal structure is expressed by a unit cell using one cobalt and two oxygens. On the other hand, as described later, the pseudospinel type crystal structure of one embodiment of the present invention is preferably expressed by a unit cell using one cobalt and one oxygen. This indicates that the symmetry of cobalt and oxygen is different in the case of the pseudospinel structure and the case of the H1-3 type structure, and the pseudospinel structure has a smaller change from the O3 structure than the H1-3 type structure. The unit cell that is more preferably used to represent the crystal structure of the positive electrode active material may be selected, for example, so that the good of fitness (GOF) value is smaller in Rietveld analysis of XRD.
[0132] When lithium cobalt oxide is repeatedly charged at a high voltage of 4.6 V or higher based on the redox potential of lithium metal, or when it is repeatedly charged to a deep depth of charge of 0.8 or higher, and then discharged, it undergoes repeated changes in crystal structure (i.e., a non-equilibrium phase change) between the H1-3 crystal structure and the R-3m(O3) structure in the discharged state.
[0133] However, these two crystal structures have a large deviation in the CoO2 layer. As shown by the dotted line and arrow in Figure 11, in the H1-3 type crystal structure, the CoO2 layer is significantly deviated from R-3m(O3). Such a dynamic structural change can have a negative effect on the stability of the crystal structure.
[0134] Furthermore, the difference in volume is large: when compared per the same number of cobalt atoms, the difference in volume between the H1-3 crystal structure and the O3 crystal structure in the discharged state is more than 3.0%.
[0135] In addition, the H1-3 crystal structure, which has continuous CoO2 layers such as P-3m1(O1), is likely to be unstable.
[0136] Therefore, the crystal structure of lithium cobalt oxide breaks down when it is repeatedly charged and discharged at high voltages. This breakage of the crystal structure causes a deterioration in cycle characteristics. This is because the number of sites where lithium can exist stably decreases and it becomes difficult to insert and remove lithium.
[0137] <Positive Electrode Active Material of One Embodiment of the Present Invention> The positive electrode active material 100 of one embodiment of the present invention can reduce the displacement of the CoO2 layer during repeated charging and discharging at high voltage. Furthermore, the change in volume can be reduced. Therefore, the positive electrode active material of one embodiment of the present invention can achieve excellent cycle characteristics. In addition, the positive electrode active material of one embodiment of the present invention can have a stable crystal structure in a high-voltage charged state. Therefore, the positive electrode active material of one embodiment of the present invention may be less likely to cause a short circuit when a high-voltage charged state is maintained. In such a case, safety is further improved, which is preferable.
[0138] In the positive electrode active material of one embodiment of the present invention, the change in crystal structure and the difference in volume per the same number of transition metal atoms between a fully discharged state and a high-voltage charged state are small.
[0139] The crystal structure of the positive electrode active material 100 before and after charging and discharging is shown in Fig. 9. The positive electrode active material 100 is a composite oxide containing lithium, cobalt as a transition metal M, and oxygen. In addition to the above, it is preferable that it contains magnesium as an additive. It is also preferable that it contains fluorine.
[0140] The crystal structure at a charge depth of 0 (discharged state) in FIG. 9 is the same as that in FIG. 11, R-3m(O3). On the other hand, when the positive electrode active material 100 is at a fully charged charge depth, it has a crystal structure different from the H1-3 type crystal structure. This structure is in the space group R-3m, and although it is not a spinel type crystal structure, ions of cobalt, magnesium, etc. occupy the oxygen 6 coordination positions, and the arrangement of cations has a symmetry similar to that of the spinel type. Therefore, this structure is referred to as a pseudo-spinel type crystal structure in this specification. In addition, although FIG. 9 shows that lithium exists at all lithium sites with the same probability, the positive electrode active material of one embodiment of the present invention is not limited to this. It may exist biasedly at some of the lithium sites. For example, Li belonging to the space group P2 / m 0.5 Like CoO2, it may be present at some of the aligned lithium sites. The distribution of lithium can be analyzed, for example, by neutron diffraction. In both the O3 type crystal structure and the pseudospinel type crystal structure, magnesium is preferably present dilutely between the CoO2 layers, that is, at the lithium sites. Fluorine is preferably present randomly and dilutely at the oxygen sites.
[0141] In addition, in the pseudospinel crystal structure, light elements such as lithium may occupy the oxygen tetracoordination site, and in this case too, the arrangement of ions has a symmetry similar to that of the spinel type.
[0142] It can also be said that the pseudo-spinel type crystal structure is a crystal structure similar to the CdCl2 type crystal structure, although it has random Li between the layers. This CdCl2 type-like crystal structure was observed when lithium nickel oxide was charged to a charge depth of 0.94 (Li 0.06The crystal structure is close to that of lithium cobalt oxide (NiO2), but it is known that pure lithium cobalt oxide or layered rock salt type positive electrode active materials that contain a large amount of cobalt do not usually have this crystal structure.
[0143] In the positive electrode active material 100 according to one embodiment of the present invention, when a large amount of lithium is released during charging at a high voltage, the change in the crystal structure is suppressed more than in conventional positive electrode active materials. For example, as shown by the dotted line in FIG. 9, there is almost no displacement of the CoO2 layer in these crystal structures.
[0144] More specifically, the positive electrode active material 100 according to one embodiment of the present invention has high structural stability even when the charging voltage is high. For example, in a conventional positive electrode active material, there is a charging voltage region where the R-3m(O3) crystal structure can be maintained even at a charging voltage where the H1-3 crystal structure is obtained, for example, at a voltage of about 4.6 V based on the potential of lithium metal, and there is a region where the pseudo-spinel crystal structure can be obtained even at a higher charging voltage, for example, at a voltage of about 4.65 V to 4.7 V based on the potential of lithium metal. When the charging voltage is further increased, the H1-3 crystal may finally be observed. Note that, in a secondary battery, when graphite is used as a negative electrode active material, for example, there is a charging voltage region where the R-3m(O3) crystal structure can be maintained even at a voltage of 4.3 V or more and 4.5 V or less, and there is a region where the pseudo-spinel crystal structure can be obtained even at a higher charging voltage, for example, at a voltage of 4.35 V or more and 4.55 V or less based on the potential of lithium metal.
[0145] Therefore, in the positive electrode active material 100 of one embodiment of the present invention, the crystal structure is not easily destroyed even when charging and discharging are repeated at a high voltage.
[0146] In addition, the pseudospinel crystal structure can be expressed by the coordinates of cobalt and oxygen in the unit cell being Co(0,0,0.5), O(0,0,x), with 0.20≦x≦0.25.
[0147] Additives such as magnesium present randomly and dilutely between the CoO2 layers, i.e., at the lithium sites, have the effect of suppressing the displacement of the CoO2 layers during charging at a high voltage. Therefore, when magnesium is present between the CoO2 layers, it is easy to form a pseudo-spinel crystal structure. Therefore, it is preferable that magnesium is distributed at an appropriate concentration throughout the positive electrode active material 100 of one embodiment of the present invention (i.e., the surface vicinity region 100a and the inner region 100b). In order to distribute magnesium throughout the positive electrode active material 100, it is preferable to perform a heat treatment in the manufacturing process of the positive electrode active material 100 of one embodiment of the present invention.
[0148] However, if the heat treatment temperature is too high, cation mixing occurs, increasing the possibility that additives, such as magnesium, will enter the cobalt site. Magnesium present in the cobalt site is ineffective in maintaining the R-3m structure during high-voltage charging. Furthermore, if the heat treatment temperature is too high, there are concerns that it may have adverse effects such as reducing cobalt to a divalent state and evaporating lithium.
[0149] Therefore, it is preferable to add a halogen compound such as a fluorine compound to the lithium cobalt oxide before the heat treatment for distributing magnesium throughout the particles. The addition of the halogen compound lowers the melting point of the lithium cobalt oxide. Lowering the melting point makes it easier to distribute magnesium throughout the particles at a temperature where cation mixing is unlikely to occur. Furthermore, the presence of a fluorine compound is expected to improve corrosion resistance against hydrofluoric acid produced by decomposition of the electrolyte.
[0150] If the magnesium concentration is increased above a desired value, the effect of stabilizing the crystal structure may be reduced. This is believed to be because magnesium enters the cobalt site in addition to the lithium site. The number of magnesium atoms in the positive electrode active material of one embodiment of the present invention is preferably 0.001 times or more and 0.1 times or less than the number of atoms of the transition metal M, more preferably greater than 0.01 and less than 0.04, and even more preferably about 0.02. Alternatively, it is preferably 0.001 times or more and less than 0.04. Alternatively, it is preferably 0.01 or more and 0.1 or less. The magnesium concentration shown here may be, for example, a value obtained by performing elemental analysis of the entire particle of the positive electrode active material using ICP-MS or the like, or may be based on the value of the raw material composition in the process of producing the positive electrode active material.
[0151] As shown in the legend in Figure 9, transition metals such as nickel and manganese and aluminum are preferably present at the cobalt site, but may be partially present at the lithium site. Magnesium is preferably present at the lithium site. Oxygen may be partially substituted with fluorine.
[0152] As the magnesium concentration of the positive electrode active material of one embodiment of the present invention increases, the charge / discharge capacity of the positive electrode active material may decrease. For example, the cause of this may be that magnesium enters the lithium site, thereby reducing the amount of lithium that contributes to charge / discharge. In addition, excessive magnesium may generate magnesium compounds that do not contribute to charge / discharge. When the positive electrode active material of one embodiment of the present invention contains nickel, the charge / discharge capacity per weight and per volume may be increased. When the positive electrode active material of one embodiment of the present invention contains aluminum, the charge / discharge capacity per weight and per volume may be increased. When the positive electrode active material of one embodiment of the present invention contains nickel and aluminum, the charge / discharge capacity per weight and per volume may be increased.
[0153] Hereinafter, the concentrations of nickel and aluminum elements in the positive electrode active material of one embodiment of the present invention will be expressed in terms of the number of atoms.
[0154] The number of nickel atoms in the positive electrode active material of one embodiment of the present invention is preferably more than 0% and 7.5% or less, more preferably 0.05% or more and 4% or less, and more preferably 0.1% or more and 2% or less, relative to the number of cobalt atoms when the number of cobalt atoms is taken as 100%. Alternatively, more than 0% and 4% or less is preferable. Alternatively, more than 0% and 2% or less is preferable. Alternatively, more than 0.05% or more and 7.5% or less is preferable. Alternatively, more than 0.1% or more and 7.5% or less is preferable. Alternatively, more than 0.1% or more and 4% or less is preferable. The nickel concentration shown here may be, for example, a value obtained by performing elemental analysis of the entire particles of the positive electrode active material using ICP-MS or the like, or may be based on the value of the composition of raw materials in the process of producing the positive electrode active material.
[0155] The number of aluminum atoms in the positive electrode active material according to one embodiment of the present invention is preferably 0.05% to 4% and more preferably 0.1% to 2% relative to the number of cobalt atoms when the number of cobalt atoms is taken as 100%. Alternatively, 0.05% to 2% is preferable. Alternatively, 0.1% to 4% is preferable. The aluminum concentration shown here may be, for example, a value obtained by performing elemental analysis of the entire particles of the positive electrode active material using ICP-MS or the like, or may be based on the value of the composition of raw materials in the process of producing the positive electrode active material.
[0156] Magnesium is preferably distributed throughout the positive electrode active material 100 of one embodiment of the present invention (i.e., the surface near region 100a and the internal region 100b), and in addition to this, as described above, the concentrations of additives and fluorine in the surface near region 100a are preferably higher than the average concentrations of additives and fluorine in the entire particle. More specifically, the concentrations of additives and fluorine in the surface near region 100a measured by XPS or the like are preferably higher than the average concentrations of additives and fluorine in the entire particle measured by ICP-MS or the like.
[0157] It is more preferable that part of the additive and fluorine contained in the positive electrode active material 100 of one embodiment of the present invention be segregated to a crystal grain boundary 101 as shown in FIG.
[0158] In other words, the concentrations of additives and fluorine at and near the crystal grain boundaries 101 of the positive electrode active material 100 of one embodiment of the present invention are preferably higher than those in other internal regions.
[0159] The grain boundary 101 is one of the planar defects. Therefore, like the grain surface, it is easily unstable and the crystal structure is likely to change. Therefore, if the concentration of additives and fluorine at and near the grain boundary 101 is high, the change in the crystal structure can be more effectively suppressed.
[0160] Furthermore, when the concentrations of additives and fluorine are high at and near the grain boundaries, even if cracks occur along the grain boundaries 101 of the particles of the positive electrode active material 100 of one embodiment of the present invention, the concentrations of additives and fluorine are high near the surface caused by the cracks. Therefore, the corrosion resistance to hydrofluoric acid can be improved even in the positive electrode active material after the cracks occur.
[0161] In this specification and the like, the vicinity of the crystal grain boundary 101 refers to a region up to about 10 nm from the grain boundary.
[0162] ≪Particle size≫ If the particle size of the positive electrode active material 100 of one embodiment of the present invention is too large, problems such as difficulty in diffusing lithium and excessive roughness of the surface of the active material layer when applied to a current collector occur. On the other hand, if the particle size is too small, problems such as difficulty in supporting the active material layer when applied to a current collector and excessive reaction with the electrolyte occur. For this reason, the average particle size (D50: also referred to as the median size) is set to Preferably, the thickness is 1 μm or more and 100 μm or less, more preferably 2 μm or more and 40 μm or less, and even more preferably 5 μm or more and 30 μm or less. Alternatively, the thickness is preferably 1 μm or more and 40 μm or less. Alternatively, the thickness is preferably 1 μm or more and 30 μm or less. Alternatively, the thickness is preferably 2 μm or more and 100 μm or less. Alternatively, the thickness is preferably 2 μm or more and 30 μm or less. Alternatively, the thickness is preferably 5 μm or more and 100 μm or less. Alternatively, the thickness is preferably 5 μm or more and 40 μm or less.
[0163] In addition, two or more positive electrode active materials 100 having different particle sizes may be mixed and used. In other words, a positive electrode active material that produces multiple peaks when the particle size distribution is measured by a laser diffraction / scattering method may be used. In this case, it is preferable to set a mixing ratio that increases the powder packing density, since this can improve the capacity per volume of the secondary battery.
[0164] <Analysis method> Whether or not a certain positive electrode active material is the positive electrode active material 100 of one embodiment of the present invention that exhibits a pseudospinel crystal structure when charged at a high voltage can be determined by analyzing the positive electrode charged at a high voltage using XRD, electron diffraction, neutron diffraction, electron spin resonance (ESR), nuclear magnetic resonance (NMR), etc. In particular, XRD is preferable in that it can analyze the symmetry of transition metals such as cobalt contained in the positive electrode active material with high resolution, it can compare the degree of crystallinity and the orientation of the crystals, it can analyze the periodic distortion of the lattice and the crystallite size, and it can obtain sufficient accuracy even when the positive electrode obtained by disassembling the secondary battery is directly measured.
[0165] As described above, the positive electrode active material 100 according to one embodiment of the present invention is characterized by the fact that there is little change in the crystal structure between the high-voltage charged state and the discharged state. Materials in which the crystal structure that changes significantly between the high-voltage charged state and the discharged state accounts for 50 wt % or more are not preferable because they cannot withstand high-voltage charging and discharging. It is also important to note that there are cases in which the desired crystal structure cannot be achieved by simply adding additives and fluorine. For example, lithium cobalt oxide containing magnesium and fluorine has a common feature that, when charged at a high voltage, the area intensity I of the H1-3 type is low. H1-3 In some cases, the percentage exceeds 70%. In addition, at a certain voltage, the pseudo-spinel crystal structure is almost 100 wt %, and when the certain voltage is further increased, the H1-3 crystal structure may be generated. Therefore, in order to determine whether or not the positive electrode active material 100 of one embodiment of the present invention is a positive electrode active material, analysis of the crystal structure, such as XRD, is required.
[0166] However, when the positive electrode active material is charged or discharged at a high voltage, its crystal structure may change when it comes into contact with the air. For example, it may change from a pseudo-spinel crystal structure to an H1-3 crystal structure. Therefore, it is preferable to handle all samples in an inert atmosphere such as an argon atmosphere.
[0167] ≪Charging method≫ High-voltage charging for determining whether a certain composite oxide is the positive electrode active material 100 of one embodiment of the present invention can be performed, for example, by preparing a coin cell (CR2032 type, diameter 20 mm, height 3.2 mm) with a lithium counter electrode and charging it.
[0168] More specifically, for the positive electrode, a slurry in which a positive electrode active material, a conductive additive, and a binder are mixed is applied to a positive electrode current collector made of aluminum foil and used.
[0169] Lithium metal can be used for the counter electrode. When a material other than lithium metal is used for the counter electrode, the voltage of the secondary battery and the potential of the positive electrode are different. Unless otherwise specified, the voltage and potential in this specification are the potential of the positive electrode.
[0170] The second electrolyte to be mixed with the first electrolyte, which is the solvent, is 1 mol / L lithium hexafluorophosphate (LiPF6), and the first electrolyte can be a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) at a volume ratio of EC:DEC = 3:7 and 2 wt% vinylene carbonate (VC).
[0171] The separator may be a 25 μm thick porous polypropylene film.
[0172] The positive electrode can and the negative electrode can may be made of stainless steel (SUS).
[0173] The coin cell prepared under the above conditions is charged at a constant current of 4.6V and 0.5C, and then charged at a constant voltage until the current value becomes 0.01C. Here, 1C is 137mA / g. Therefore, if the amount of active material of the positive electrode of one coin cell is 10mg, it corresponds to charging at 0.685mA. In order to observe the phase change of the positive electrode active material, it is desirable to charge at such a small current value. The temperature is 25°C. After charging in this way, the coin cell is disassembled in a glove box in an argon atmosphere and the positive electrode is taken out, and a positive electrode active material charged at a high voltage is obtained. When various analyses are performed after this, it is preferable to seal the disassembled positive electrode in an argon atmosphere in order to suppress reactions with external components. For example, XRD can be performed by sealing the disassembled positive electrode in an airtight container for XRD measurement in an argon atmosphere.
[0174] <XRD> Ideal powder XRD patterns calculated from the pseudo-spinel crystal structure and the H1-3 crystal structure model using CuKα1 radiation are shown in Figures 10 and 12. For comparison, ideal XRD patterns calculated from the crystal structures of LiCoO2(O3) at charge depth 0 and CoO2(O1) at charge depth 1 are also shown. The patterns of LiCoO2(O3) and CoO2(O1) were created using Reflex Powder Diffraction, one of the modules of Materials Studio (BIOVIA), from crystal structure information obtained from ICSD (Inorganic Crystal Structure Database) (see Non-Patent Document 5). The 2θ range was 15° to 75°, Step size = 0.01, and wavelength λ1 = 1.540562 × 10 -10 m and λ2 were not set, and Monochromator was set to single. The pattern of the H1-3 type crystal structure was similarly created from the crystal structure information described in Non-Patent Document 3. The pattern of the pseudo-spinel type crystal structure was estimated from the XRD pattern of the positive electrode active material of one embodiment of the present invention, and fitting was performed using TOPAS ver.3 (crystal structure analysis software manufactured by Bruker) to create an XRD pattern in the same manner as the others.
[0175] As shown in Figure 10, in the pseudo-spinel crystal structure, diffraction peaks appear at 2θ = 19.30 ± 0.20° (19.10° to 19.50°) and 2θ = 45.55 ± 0.10° (45.45° to 45.65°). More specifically, sharp diffraction peaks appear at 2θ = 19.30 ± 0.10° (19.20° to 19.40°) and 2θ = 45.55 ± 0.05° (45.50° to 45.60°). However, as shown in Figure 12, in the H1-3 crystal structure and CoO2 (P-3m1, O1), no peaks appear at these positions. Therefore, the appearance of peaks at 2θ=19.30±0.20° and 2θ=45.55±0.10° in a state charged at a high voltage can be said to be a characteristic of the positive electrode active material 100 of one embodiment of the present invention.
[0176] This can also be said to be because the positions at which the XRD diffraction peaks appear are close between the crystal structure at a charge depth of 0 and the crystal structure when charged at a high voltage. More specifically, the difference in the positions at which the peaks appear for two or more, more preferably three or more, of the main diffraction peaks of both structures is 2θ=0.7 or less, more preferably 2θ=0.5 or less.
[0177] In addition, the sharpness of the diffraction peaks in the XRD pattern indicates the high crystallinity. Therefore, it is preferable that each diffraction peak after charging is sharp, that is, the half-width is narrow. The half-width varies depending on the XRD measurement conditions and the value of 2θ, even for peaks generated from the same crystal phase. In the case of the above-mentioned measurement conditions, the half-width of the peaks observed at 2θ=43° or more and 46° or less is preferably 0.2° or less, more preferably 0.15° or less, and even more preferably 0.12° or less. It is not necessary that all peaks meet this requirement. If some peaks meet this requirement, it can be said that the crystallinity of the crystal phase is high. Therefore, it contributes sufficiently to the stabilization of the crystal structure after charging.
[0178] Note that the positive electrode active material 100 of one embodiment of the present invention has a pseudo-spinel crystal structure when charged at a high voltage, but not all of the particles need to have a pseudo-spinel crystal structure, and may include other crystal structures or may be partially amorphous.
[0179] For example, when charging at 4.6 V, the area intensity ratio of the H1-3 type peak to the pseudo-spinel type peak is compared, and it is sufficient if the H1-3 type peak is below a certain level. Alternatively, it is sufficient if the area intensity ratio of the H1-3 type peak to the pseudo-spinel type and LiCoO2 O3 type peak is above a certain level.
[0180] For example, the H1-3 type has a peak at 2θ=19.69°±0.2° corresponding to the (006) plane. The pseudo-spinel type and the O3 type of LiCoO2 have a peak at 2θ=19.30±0.20° corresponding to the (003) plane. Therefore, among the integrated intensities in the range of 2θ between 18° and 20°, the peaks below 19.30° can be considered to be the integrated intensities of the pseudo-spinel type and the O3 type. The integrated intensity ratio I H1-3(006) / I 擬スピネル+O3(003) is preferably 70% or less, more preferably 50% or less, and even more preferably 40% or less. With such an area intensity ratio, a positive electrode active material having sufficiently excellent charge-discharge cycle characteristics can be obtained.
[0181] In addition, the H1-3 type has a peak corresponding to the (107) plane at 2θ=43.83°±0.2°. In addition, the pseudospinel and O3 types have a peak corresponding to the (104) plane at 2θ=45.55°±0.2°. Therefore, among the integrated intensities in the range of 2θ between 43° and 46°, the peaks above 44.50° can be considered to be the integrated intensities of the pseudospinel and O3 types. The integrated intensity ratio I H1-3(107) / I 擬スピネル+O3(104)is preferably 50% or less, more preferably 40% or less, and even more preferably 30% or less. With such an area intensity ratio, a positive electrode active material having sufficiently excellent charge-discharge cycle characteristics can be obtained. The peaks corresponding to the (107) plane of the H1-3 type and the (104) plane of the pseudospinel type are easily separated from other peaks, and are suitable for comparing peak intensity ratios.
[0182] In addition, the crystallite size of the pseudo-spinel crystal structure of the positive electrode active material particles only decreases to about 1 / 10 of that of LiCoO2(O3) in the discharged state. Therefore, even under the same XRD measurement conditions as the positive electrode before charging and discharging, a clear pseudo-spinel crystal structure peak can be confirmed after high-voltage charging. On the other hand, in the case of simple LiCoO2, even if some of it can take on a structure similar to the pseudo-spinel crystal structure, the crystallite size becomes smaller upon high-voltage charging, and the XRD peak becomes broad and small. The crystallite size can be determined from the half-width of the XRD peak.
[0183] As described above, the positive electrode active material of one embodiment of the present invention is preferably small in influence of the Jahn-Teller effect. The positive electrode active material of one embodiment of the present invention preferably has a layered rock salt type crystal structure and mainly contains cobalt as a transition metal. In addition, the positive electrode active material of one embodiment of the present invention may contain the above-mentioned additives, nickel and manganese, in addition to cobalt, as long as the influence of the Jahn-Teller effect is small.
[0184] The peaks appearing in the powder XRD pattern reflect the crystal structure of the internal region 100b of the positive electrode active material 100, which occupies most of the volume of the positive electrode active material 100. The crystal structure of the surface vicinity region 100a can be analyzed by electron diffraction of a cross section of the positive electrode active material 100, or the like.
[0185] EPMA EPMA (Electron Probe Microanalysis) allows for the quantification of elements. Area analysis allows for the distribution of each element to be analyzed.
[0186] EPMA analyzes the area from the surface to a depth of about 1 μm. Therefore, the concentration of each element may differ from the measurement results using other analytical methods. For example, when performing a surface analysis of the positive electrode active material 100, the concentration of the additive present in the surface vicinity region may be lower than the result of XPS. Also, the concentration of the additive present in the surface vicinity region may be higher than the result of ICP-MS or the value of the raw material composition in the process of manufacturing the positive electrode active material.
[0187] When a cross section of the positive electrode active material 100 according to one embodiment of the present invention is analyzed by EPMA, the additive preferably has a concentration gradient that increases from the inner region toward the surface near region. More specifically, as shown in FIG. 2(B1), magnesium, fluorine, titanium, and silicon preferably have a concentration gradient that increases from the inner region toward the surface. Also, as shown in FIG. 3(C2), aluminum preferably has a concentration peak in a region deeper than the concentration peaks of the above elements. The aluminum concentration peak may be present in the surface near region or may be deeper than the surface near region.
[0188] Note that the surface and near-surface region of the positive electrode active material of one embodiment of the present invention do not include carbonic acid, hydroxyl groups, etc. that are chemically adsorbed after the preparation of the positive electrode active material. Also, the electrolyte, binder, conductive material, or compounds derived therefrom that are attached to the surface of the positive electrode active material are not included. Therefore, when quantifying elements contained in the positive electrode active material, correction may be made to exclude carbon, hydrogen, excess oxygen, excess fluorine, etc. that can be detected by surface analysis such as XPS and EPMA.
[0189] <Surface roughness and specific surface area> The positive electrode active material 100 according to one embodiment of the present invention preferably has a smooth surface with few irregularities. A smooth surface with few irregularities is one factor indicating that the additive is well distributed in the surface near region 100a.
[0190] Whether the surface is smooth and has few projections and recesses can be determined, for example, from a cross-sectional SEM image or cross-sectional TEM image of the positive electrode active material 100, the specific surface area of the positive electrode active material 100, or the like.
[0191] For example, the surface smoothness can be quantified from a cross-sectional SEM image of the positive electrode active material 100 as follows.
[0192] First, the cathode active material 100 is processed by FIB or the like to expose the cross section. At this time, it is preferable to cover the cathode active material 100 with a protective film, a protective agent, or the like. Next, an SEM image of the interface between the protective film or the like and the cathode active material 100 is taken. The SEM image is subjected to noise processing using image processing software. For example, Gaussian blurring (σ=2) is performed, and then binarization is performed. Furthermore, interface extraction is performed using image processing software. Furthermore, the interface line between the protective film or the like and the cathode active material 100 is selected using a magic hand tool or the like, and data is extracted to a spreadsheet software or the like. Using the functions of the spreadsheet software or the like, correction is performed from the regression curve (quadratic regression), and a parameter for calculating roughness is obtained from the data after the slope correction, and the root mean square surface roughness (RMS) is calculated by calculating the standard deviation. In addition, this surface roughness is the surface roughness at least at 400 nm of the outer periphery of the particle of the cathode active material.
[0193] The particle surfaces of the positive electrode active material 100 of this embodiment preferably have a roughness index (RMS: root mean square surface roughness) of less than 3 nm, preferably less than 1 nm, and more preferably less than 0.5 nm.
[0194] The image processing software used for noise processing, boundary extraction, etc. is not particularly limited, but for example, "ImageJ" can be used. The spreadsheet software is also not particularly limited, but for example, Microsoft Office Excel can be used.
[0195] For example, the actual specific surface area A measured by the constant volume gas adsorption method R and the ideal specific surface area A i The smoothness of the surface of the positive electrode active material 100 can also be expressed as a numerical value based on the ratio of the surface smoothness to the surface smoothness.
[0196] Ideal specific surface area A iis calculated assuming that all particles have the same diameter, the same weight, and an ideal spherical shape.
[0197] The median diameter D50 can be measured by a particle size distribution meter using a laser diffraction / scattering method, etc. The specific surface area can be measured by a specific surface area measuring device using a gas adsorption method by a constant volume method, for example.
[0198] The positive electrode active material 100 according to one embodiment of the present invention has an ideal specific surface area A calculated from the median diameter D50. i and the actual specific surface area A R Ratio of A R / A i It is preferable that the ratio is 2 or less.
[0199] FIG. 4A is a schematic diagram of the vicinity of a current collector during charging in the case where a secondary battery is manufactured using the positive electrode active material 100 of one embodiment of the present invention.
[0200] FIG. 4 illustrates a current collector, a positive electrode active material 100, and graphene as a conductive additive. Since the electric field relaxation region 103 is dotted or scattered near the surface of the positive electrode active material 100, electrons can be exchanged between the current collector, the graphene in contact with the current collector, and the positive electrode active material 100 in contact with the graphene. In addition, the positive electrode active material 100 is provided with the electric field relaxation region 103, which can reduce the occurrence of a strong potential difference between the positive electrode active material 100 and the electrolyte adjacent to the positive electrode active material 100. Therefore, by forming the electric field relaxation region 103 between the positive electrode active material 100 and the electrolyte, a secondary battery that is electrochemically stable at a high potential can be realized.
[0201] A lithium ion secondary battery using an electrolyte has a positive electrode, a negative electrode, a separator, an electrolyte, and an exterior body. In a lithium ion secondary battery, the anode (positive electrode) and the cathode (negative electrode) are interchanged during charging and discharging, and the oxidation reaction and the reduction reaction are interchanged, so the electrode with a high reaction potential is called the positive electrode, and the electrode with a low reaction potential is called the negative electrode. Therefore, in this specification, the positive electrode is called the "positive electrode" or "+ electrode (plus electrode)" and the negative electrode is called the "negative electrode" or "- electrode (minus electrode)" whether during charging, discharging, when a reverse pulse current is applied, or when a charging current is applied. If the terms anode (positive electrode) and cathode (negative electrode) related to the oxidation reaction and reduction reaction are used, they may be reversed during charging and discharging, which may cause confusion. Therefore, the terms anode (positive electrode) and cathode (negative electrode) are not used in this specification. If the terms anode and cathode are used, it should be specified whether they are used during charging or discharging, and also whether they correspond to the positive electrode (plus) or negative electrode (minus).
[0202] FIG. 4B is a schematic cross-sectional view of a lithium ion secondary battery during charging.
[0203] A charger is connected to the two terminals shown in Fig. 4(B) and the storage battery 1400 is charged. As the charging of the storage battery 1400 progresses, the potential difference between the electrodes increases. In Fig. 4(B), the positive direction is the direction of current that flows from an external terminal of the storage battery 1400 to the positive electrode 1402, flows from the positive electrode 1402 to the negative electrode 1404 inside the storage battery 1400, and then flows from the negative electrode to an external terminal of the storage battery 1400. In other words, the direction of flow of the charging current is the direction of the current.
[0204] During charging, lithium ions accumulate in the negative electrode. The charging capacity of the negative electrode is required to be larger than that of the positive electrode. In the first stage, lithium ions move in the order of the negative electrode, electrolyte, and positive electrode during discharge. In the second stage, electrons move in the external circuit in the order of the negative electrode and positive electrode. Current flows from the positive electrode to the negative electrode. In the third stage, lithium ions gather on the positive electrode side, and electrons are released from the outside via the electrode and conductive additives such as graphene and CNT in materials such as LCO and MCN to the positive electrode material, where they are ionized and neutralized with the lithium ions. In the fourth stage, the lithium ions and electrons are neutralized, and the lithium diffuses into the positive electrode material. The fact that this penetration is not necessarily uniform causes a major problem. For example, in rapid discharge, lithium ions may enter part of the positive electrode material, resulting in an uneven state. In addition, many electrons gather near the current collector of the positive electrode active material layer. Conductive additives such as graphene and CNT are scattered in the positive electrode active material layer. Therefore, a countermeasure can be taken in which a low-viscosity electrolyte is filled into the voids in the positive electrode active material layer to facilitate smooth movement of lithium ions.
[0205] When a large voltage is applied to the positive electrode, the positive electrode becomes the high potential side and the negative electrode becomes the low potential side. When lithium ions are released from the positive electrode, the electrons move to the external circuit via conductive additives such as graphene and CNT. The lithium ions dissolve into the electrolyte. When lithium ions diffuse, the crystals expand to a certain extent at that location. In addition, a potential is created between the electrolyte and the positive electrode. When a large amount of lithium ions enter the positive electrode material, in addition to the positive electrode material itself expanding, the cobalt element reacts with oxygen (dispersed with the bulk) and dissolves into the electrolyte due to electric field drift. It is expected that the material that gives ferroelectricity will relax the electric field and block the dissolution of cobalt and other elements into the electrolyte. When the charge becomes large, a high potential difference (potential) is created at the positive electrode-electrolyte interface. The high potential difference can be mitigated by providing a material that gives ferroelectricity as a shell, or by dotting or scattering the material that gives ferroelectricity on the surface.
[0206] In order to create a shell structure with a ferroelectric material as the shell, the technology of coating the ferroelectric material is important. If the high potential difference is alleviated by the ferroelectric material, the potential difference at the positive electrode-electrolyte interface is reduced. This eliminates or reduces the dissolution of cobalt and other elements. Even if the LCO is charged to a charging voltage of 4.7 V or more, or even 5.0 V or more, and the strain of the LCO increases, if there is no potential difference on the LCO surface, it will not dissolve to the outer electrolyte side.
[0207] Examples of materials that can be made ferroelectric include HfZrO X (X>0) and HfZrO X (X>0) can be used. The material having ferroelectricity can be a two-layer structure, a multi-layer structure, an alloy structure, or a mixture or combination of these. ZrO X The (X>0) system is more stable when alloyed.
[0208] Even if there is a material that gives ferroelectricity locally on the surface of the positive electrode member, it is possible to create an electric field relaxation region between the positive electrode member and the electrolyte by providing a certain amount of electric field relaxation around it. Therefore, charging at a certain high voltage is possible. Also, even if it is locally localized like a mesh or checkerboard, it is possible to provide multiple materials that give ferroelectricity and allow lithium ions to freely enter and exit through the gaps in the electric field relaxation region.
[0209] When the LCO deteriorates, the crystals of the LCO itself break down, causing the problem of cobalt and other elements dissolving into the electrolyte. If conductive additives such as graphene and CNT are in close contact with the outside of the shell, the positive electrode will be at its largest during discharge, and the crystals will expand and become more susceptible to destruction. This is because the Co-O bond becomes weak, especially at high temperatures such as 85°C. Therefore, in order to prevent outward diffusion of the broken positive electrode material, ε S It is preferable to use a material having a large electric field, particularly a material having ferroelectricity, to relax the electric field. By providing a region for relaxing the electric field, it is possible to suppress the elution of cobalt.
[0210] The dielectric constant ε of a material that has ferroelectric properties S is 10 or more, preferably 15 or more and less than 5000. The material to be made ferroelectric is in contact with or close to the positive electrode material such as LCO or NCM. The dielectric constant ε of the material to be made ferroelectric is S When the dielectric constant is relatively large, the material is fixed and the electric field can be relaxed. Therefore, a high dielectric constant is particularly preferable.
[0211] The material that imparts ferroelectricity is an inorganic compound, has a dielectric constant greater than that of the inside of the positive electrode active material, and can also be fixed as a non-conductive material that does not actively have a lithium ion storage function during charging and discharging.
[0212] Before forming the material that gives ferroelectricity, the positive electrode particles may have defects, cracks, etc., and it is effective to localize the reinforcing additive elements Mg, Al, and F in these particles to prevent the cracks of defects from increasing. The material that gives ferroelectricity is attached to cover them, or is dotted or scattered. By providing the material that gives ferroelectricity on the surface of these particles on the side that contacts the electrolyte and alleviating the electric field on the side that contacts the electrolyte, it is possible to prevent or reduce the deterioration elements of the positive electrode (Co, Ni, Mn, O, etc.) from dissolving into the electrolyte due to electric field damage. When using a material that gives ferroelectricity to form a shell structure, it is preferable that particles with large and small particle sizes are scattered and attached to the larger particles in the positive electrode, as this is less likely to be damaged than the positive electrode member itself.
[0213] In addition, there is a gap (space) inside the positive electrode where an electrolyte containing lithium ions exists, and the lithium ions are injected into the positive electrode particles from this gap. Therefore, it is preferable to provide a material that has ferroelectricity in the area where the lithium ions frequently enter and exit from this space, thereby forming a structure that relaxes the electric field.
[0214] It is effective to locally or entirely attach or coat the positive electrode components such as LCO or MCN with a material that imparts ferroelectricity, in order to prevent breakdown during charging and discharging and to increase the withstand voltage.
[0215] In this embodiment, an example of a lithium ion secondary battery is shown, but the present invention is not limited to lithium ion secondary batteries, and can also be applied to secondary batteries that use an alkali metal such as sodium or potassium instead of lithium.
[0216] As the negative electrode active material, an element capable of carrying out a charge / discharge reaction by alloying / dealloying with lithium can be used. For example, a material containing at least one of silicon, tin, gallium, aluminum, germanium, lead, antimony, bismuth, silver, zinc, cadmium, indium, etc. can be used. Such elements have a larger capacity than carbon, and silicon in particular has a high theoretical capacity of 4200mAh / g.
[0217] In addition, when silicon is used for the negative electrode, an amorphous and elastic protective film is preferable. For example, amorphous SiO X and graphene are preferred.
[0218] The secondary battery may also have a separator to prevent short circuits. Examples of the separator include fibers containing cellulose such as paper, nonwoven fabrics, glass fibers, ceramics, and synthetic fibers using nylon (polyamide), vinylon (polyvinyl alcohol fiber), polyester, acrylic, polyolefin, and polyurethane.
[0219] In addition, when forming a positive electrode active material layer or a negative electrode active material layer, a slurry is used and applied onto the current collector. The slurry is a material liquid used to form an active material layer on the current collector 550, and contains at least an active material, a binder, and a solvent, and preferably further includes a conductive assistant. The slurry is sometimes called an electrode slurry or an active material slurry, and when forming a positive electrode active material layer, it is sometimes called a positive electrode slurry, and when forming a negative electrode active material layer, it is sometimes called a negative electrode slurry.
[0220] The conductive assistant is also called a conductive agent or conductive material, and is made of a carbon material. By attaching the conductive assistant between a plurality of active materials, the plurality of active materials are electrically connected to each other, and the conductivity is increased. Note that the term "attachment" does not only refer to physical adhesion between the active material and the conductive assistant, but also includes cases where a covalent bond is formed, where the conductive assistant is bonded by van der Waals forces, where a part of the surface of the active material is covered by the conductive assistant, where the conductive assistant is embedded in the surface irregularities of the active material, and where the active material is electrically connected even if they are not in contact with each other.
[0221] A typical carbon material used as a conductive additive is carbon black (furnace black, acetylene black, graphite, etc.).
[0222] In order to bond the current collector, such as a metal foil, and the active material to the positive electrode of a secondary battery, a binder (resin) is mixed in. The binder is also called a binding material. The binder is a polymer material, and if a large amount of the binder is added, the ratio of the active material in the positive electrode decreases, and the discharge capacity of the secondary battery decreases. Therefore, the amount of the binder is kept to a minimum.
[0223] In this specification and the like, the binder refers to a polymer compound that is mixed only to bind the active material, conductive material, etc., onto the current collector, such as rubber materials such as polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR), styrene-isoprene-styrene rubber, butadiene rubber, ethylene-propylene-diene copolymer, fluororubber, polystyrene, polyvinyl chloride, polytetrafluoroethylene, polyethylene, polypropylene, polyisobutylene, ethylene propylene diene polymer, and the like.
[0224] Since lithium ion conductive polymers are polymer compounds, by mixing them well and using them in the positive electrode active material layer, it becomes possible to bind the positive electrode active material and conductive material onto the positive electrode current collector. Therefore, a positive electrode can be produced without using a binder. Binders are materials that do not contribute to charge / discharge reactions. Therefore, the less binder there is, the more materials that contribute to charge / discharge, such as active materials and electrolytes, can be increased. This allows for a secondary battery with improved discharge capacity or cycle characteristics.
[0225] This embodiment mode can be used in combination with other embodiment modes.
[0226] (Embodiment 2) In this embodiment, a positive electrode active material 104 shown in FIG. 1B will be described below as an example different from the positive electrode active material 100 in Embodiment 1.
[0227] The positive electrode active material 104 has crystal grain boundaries 101 therein, and has a surface vicinity region 100a and an inner region 100b. It also has an electric field relaxation region 103 that is a covering film (also called a coating film). Although Fig. 1(B) shows the electric field relaxation region 103 having a uniform film thickness over the entire surface of the positive electrode active material 100, this is not particularly limited, and it may have a partially thin portion or a partially thick portion.
[0228] Furthermore, when the dielectric constant of the electric field relaxation region 103 is high, the electric field relaxation function can be sufficiently exhibited even if the thickness of the electric field relaxation region 103 is thin. In particular, when the electric field relaxation region 103 is formed thin, it is preferable that the surface before the formation of the electric field relaxation region 103 is smooth and has few irregularities. When the electric field relaxation region 103 is formed on a surface that is smooth and has few irregularities, the surface can also be made smooth and has few irregularities. The fact that the surface is smooth and has few irregularities can be judged, for example, from a cross-sectional SEM image or cross-sectional TEM image of the positive electrode active material 104, the specific surface area of the positive electrode active material 104, etc. The particle shape of the positive electrode active material 104 is rarely spherical, but is irregular, so it is difficult to determine the radius of curvature, and it is also difficult to define it because the radius of curvature changes as the particle size changes. However, in a cross-sectional shape obtained by cutting the positive electrode active material 104 at any position, the shape has almost no sharp edges and the edges are rounded. In this way, fluorine is important for making the surface smooth or shiny, and creates clean bonds on the surface. Fluorine improves the wettability of the positive electrode active material surface, making it homogenous and flat. For example, it is important to prepare positive electrode active material particles by mixing lithium oxide and fluoride and heating them.
[0229] If there are areas on the surface of the positive electrode active material particles where pure LiCoO2 is exposed, unevenness will also occur, and cobalt and oxygen will be released during charging and discharging, causing the crystal structure to collapse and degradation. It is preferable to uniformly cover the surface with a compound containing magnesium so that the areas where pure LiCoO2 is exposed are not exposed on the surface. Magnesium has the function of maintaining the crystal structure (layered rock salt type crystal structure) even if Li is released during discharging. Another feature is the presence of magnesium (or fluorine) within the vicinity of the surface of the positive electrode active material particles.
[0230] Moreover, when the dielectric constant of the electric field relaxation region 103 is low, the electric field relaxation function can be sufficiently exhibited by making the film thicker. Therefore, it is preferable to adjust the film thickness appropriately depending on the material of the electric field relaxation region 103 according to the application of the secondary battery.
[0231] The positive electrode active material 104 can provide the effect of alleviating an electric field, similar to the positive electrode active material 100 .
[0232] In addition, a positive electrode active material 105 shown in FIG. 1C is an example different from those in FIGS. 1A and 1B.
[0233] The positive electrode active material 105 has a crystal grain boundary 101 therein, and has a mixed region 106 and an inner region 100b. The mixed region 106 indicates a region where the compositions of the surface near region 100a and the electric field relaxation region 103 in FIG. 1(A) and FIG. 1(B) are distributed in a complex manner. For example, the positive electrode active material 105 can be obtained by subjecting the positive electrode active material 100 in FIG. 1(A) to a heat treatment to partially melt the materials contained in the surface near region 100a and the electric field relaxation region 103 that is a convex portion. Depending on the heat treatment and the material contained in the electric field relaxation region 103, the electric field relaxation region 103 that is a convex portion may be integrated with the surface near region 100a to form the mixed region 106.
[0234] 1B, a heat treatment is applied to the positive electrode active material 104 to partially melt the materials contained in the surface vicinity region 100a and the electric field relaxation region 103, thereby obtaining a positive electrode active material 105. The heat treatment hardly changes the inner region 100b, but the outer region may have a lower melting point due to the combination of various elements, and may be partially melted to form an alloy. The mixed region 106 is a coating film (also called a coating film) and partially or entirely functions as an electric field relaxation region.
[0235] The positive electrode active material 105 can provide the effect of alleviating an electric field, similar to the positive electrode active material 100 .
[0236] This embodiment mode can be freely combined with other embodiment modes.
[0237] (Embodiment 3) FIG. 3 shows an example of a positive electrode active material 100 having a region containing an alloy according to one embodiment of the present invention.
[0238] Fig. 5(A) is a schematic top view of a positive electrode active material 100 having an electric field relaxation region 103 that is a convex portion as a region where one or more types of additive elements are unevenly distributed, which is one embodiment of the present invention. Fig. 5(B) or Fig. 5(C) shows a schematic cross-sectional view taken along line EF in Fig. 5(A). Note that a convex portion may be any portion that has a different height from the other portions, and may also be called a water droplet-shaped portion, a colony-shaped portion, a hill-shaped portion, or the like. In addition, when there are multiple convex portions, the shapes do not have to be uniform.
[0239] The electric field relaxation region 103 in the form of a convex portion is preferably present on the surface of the positive electrode active material 100. When the positive electrode active material 100 contains both fluorine and a compound of a metal such as magnesium and titanium as impurities (or added elements), the electric field relaxation region 103 in the form of a convex portion preferably has a high fluorine concentration region 103a and a high metal element concentration region 103b as shown in FIG. 3(B). The high fluorine concentration region 103a has a higher fluorine concentration than the entire positive electrode active material 100 and the high metal element concentration region 103b. The high metal element concentration region 103b has a higher metal concentration than the entire positive electrode active material 100 and the high fluorine concentration region 103a. The positive electrode active material 100 preferably has a high metal element concentration region 103b on the positive electrode active material 100 so as to cover the high fluorine concentration region 103a.
[0240] It is preferable that impurities (or additive elements) such as titanium, magnesium, and fluorine are present at appropriate concentrations in the surface vicinity region 100a of the positive electrode active material 100. It is preferable that the impurities (or additive elements) have a concentration gradient that increases from the inside of the positive electrode active material 100 toward the surface.
[0241] When positive electrode active material 100 contains nickel as transition metal M, a part of the nickel may be present in metal element high concentration region 103b. In this case, metal element high concentration region 103b has a higher nickel concentration than positive electrode active material 100 as a whole and high fluorine concentration region 103a.
[0242] 5(C), nickel-rich region 100d may be present in a portion of positive electrode active material 100 overlapping electric field relaxation region 103 which is a convex portion. Nickel-rich region 100d can be considered as a trace of nickel dissolved in the positive electrode active material 100 and attracted to electric field relaxation region 103 which is a convex portion. Nickel-rich region 100d has a higher nickel concentration than the portions of positive electrode active material 100 other than nickel-rich region 100d, and a lower nickel concentration than metal element-rich region 103b.
[0243] Also, all impurities (or additive elements) do not have to have the above-mentioned distribution. For example, when the positive electrode active material 100 contains aluminum as an impurity (or additive element), it is preferable that the aluminum has a distribution different from that of magnesium or titanium. For example, it is preferable that aluminum is hardly unevenly distributed in the electric field relaxation region 103 that is a convex portion, but is present in the surface vicinity region 100a of the positive electrode active material 100. In other words, it is preferable that the aluminum concentration in the surface vicinity region 100a is higher than the aluminum concentration in the electric field relaxation region 103 that is a convex portion.
[0244] In the present specification and the like, the electric field relaxation region 103, which is a convex portion of the positive electrode active material 100, refers to a region having a different composition from the positive electrode active material 100. The positive electrode active material 100 and the region where the excess impurities (or added elements) are unevenly distributed may have different crystal structures. For example, the positive electrode active material 100 may have a layered rock salt crystal structure, and the region where the excess impurities (or added elements) are unevenly distributed may have a rock salt, spinel, rutile, or anatase crystal structure. The regions having different compositions or crystal structures can be determined by various analyses including EDX, cross-sectional TEM, surface SEM, and electron beam diffraction.
[0245] Furthermore, lithium, transition metals, and oxygen that are not contained in the impurities (or added elements) are preferably uniformly distributed in the positive electrode active material 100. In this specification and the like, "uniform" means that it is sufficient for the difference in element concentration to be substantially uniform, for example, within 10%.
[0246] Regarding the concentration gradient of impurities (or added elements) in the surface vicinity region 100a in the positive electrode active material 100 in FIG. 6, the descriptions in FIG. 2 and FIG. 3 can be referred to.
[0247] In this embodiment, an example of a method for producing a positive electrode active material 100 shown in FIG. 6, which contains cobalt and nickel as transition metals M, and further contains magnesium, a plurality of additive elements (nickel, aluminum, titanium, etc.), and fluorine, will be described.
[0248] <Step S11> In step S11 of FIG. 5, first, a lithium source and a transition metal M source are prepared as materials for a composite oxide (LiMO2) having lithium, a transition metal M, and oxygen.
[0249] As the lithium source, for example, lithium carbonate, lithium fluoride, etc. can be used.
[0250] As the transition metal M, it is preferable to use a metal that can form a layered rock-salt type composite oxide belonging to the space group R-3m together with lithium. For example, at least one of manganese, cobalt, and nickel can be used. In other words, as the source of the transition metal M, only cobalt may be used, only nickel may be used, two types of cobalt and manganese, two types of cobalt and nickel, or three types of cobalt, manganese, and nickel may be used.
[0251] When using metals capable of forming a layered rock-salt type composite oxide, it is preferable to mix cobalt, manganese, and nickel in a ratio that allows a layered rock-salt type crystal structure to be formed. Aluminum may also be added to these transition metals in a ratio that allows a layered rock-salt type crystal structure to be formed.
[0252] As the transition metal M source, oxides, hydroxides, etc. of the above-mentioned metals exemplified as the transition metal M can be used. As the cobalt source, for example, cobalt oxide, cobalt hydroxide, etc. can be used. As the manganese source, manganese oxide, manganese hydroxide, etc. can be used. As the nickel source, nickel oxide, nickel hydroxide, etc. can be used. As the aluminum source, aluminum oxide, aluminum hydroxide, etc. can be used.
[0253] <Step S12> Next, in step S12, the lithium source and the transition metal M source are mixed. The mixing can be performed in a dry or wet manner. For example, a ball mill, a bead mill, or the like can be used for mixing. When using a ball mill, it is preferable to use, for example, zirconia balls as the grinding media.
[0254] <Step S13> Next, in step S13, the material mixed above is heated. This step may be called the first heating or firing to distinguish it from the subsequent heating step. In the first heating, the material is placed in an alumina crucible, covered, and heated in a muffle furnace. The heating is preferably performed at 800°C or higher and lower than 1100°C, more preferably at 900°C or higher and 1000°C or lower, and even more preferably at about 950°C. Alternatively, 800°C or higher and 1000°C or lower are preferable. Alternatively, 900°C or higher and 1100°C or lower are preferable. If the temperature is too low, the decomposition and melting of the lithium source and the transition metal M source may be insufficient. On the other hand, if the temperature is too high, defects may occur due to excessive reduction of the metal used as the transition metal M, which is responsible for the redox reaction, or lithium evaporating. For example, if cobalt is used as the transition metal M, defects may occur in which cobalt becomes divalent.
[0255] The heating time can be, for example, 1 hour to 100 hours, preferably 2 hours to 20 hours. Alternatively, 1 hour to 20 hours is preferable. Alternatively, 2 hours to 100 hours is preferable. The firing is preferably performed in an atmosphere with little water such as dry air (for example, a dew point of -50°C or less, more preferably -100°C or less). For example, the material is heated at 1000°C for 10 hours, and the temperature rise is preferably 200°C / h and the flow rate of the dry atmosphere is preferably 10 L / min. The heated material can then be cooled to room temperature (25°C). For example, the temperature drop time from a specified temperature to room temperature is preferably 10 hours to 50 hours.
[0256] However, cooling to room temperature in step S13 is not essential, and cooling may be performed to a temperature higher than room temperature if there is no problem in performing the subsequent steps S41 to S43.
[0257] The first heating may be carried out either continuously or batchwise.
[0258] <Step S14> Next, in step S14, the material obtained by the first heating is recovered to obtain a composite oxide (LiMO2) having lithium, a transition metal M, and oxygen. Specifically, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium cobalt oxide in which a portion of the cobalt is replaced by manganese, lithium cobalt oxide in which a portion of the cobalt is replaced by nickel, or lithium nickel-manganese-cobalt oxide is obtained.
[0259] Alternatively, a composite oxide containing lithium, a transition metal M, and oxygen that has been synthesized in advance may be used in step S14. In this case, steps S11 to S13 may be omitted.
[0260] For example, lithium cobalt oxide particles (product name: Cellseed C-10N) manufactured by Nippon Chemical Industry Co., Ltd. can be used as a pre-synthesized composite oxide. This is lithium cobalt oxide with an average particle diameter (D50) of about 12 μm, and in elemental analysis by glow discharge mass spectrometry (GD-MS), the magnesium concentration and fluorine concentration are 50 ppm wt or less, the calcium concentration, aluminum concentration and silicon concentration are 100 ppm wt or less, the nickel concentration is 150 ppm wt or less, the sulfur concentration is 500 ppm wt or less, the arsenic concentration is 1100 ppm wt or less, and the concentrations of other elements other than lithium, cobalt and oxygen are 150 ppm wt or less.
[0261] Alternatively, lithium cobalt oxide particles (product name: Cellseed C-5H) manufactured by Nippon Chemical Industry Co., Ltd. can also be used. This is lithium cobalt oxide with an average particle size (D50) of about 6.5 μm, and in elemental analysis by GD-MS, the concentration of elements other than lithium, cobalt, and oxygen is similar to or lower than that of C-10N.
[0262] In this embodiment, cobalt is used as the metal M, and pre-synthesized lithium cobalt oxide particles (Cellseed C-10N manufactured by Nippon Chemical Industry Co., Ltd.) are used.
[0263] <Step S21> Next, in step S21, a halogen source such as a fluorine source or a chlorine source, and a magnesium source are prepared as materials for the mixture 902. It is also preferable to prepare a lithium source.
[0264] Examples of fluorine sources that can be used include lithium fluoride (LiF), magnesium fluoride (MgF2), aluminum fluoride (AlF3), titanium fluoride (TiF4), cobalt fluoride (CoF2, CoF3), nickel fluoride (NiF2), zirconium fluoride (ZrF4), vanadium fluoride (VF5), manganese fluoride, iron fluoride, chromium fluoride, niobium fluoride, zinc fluoride (ZnF2), calcium fluoride (CaF2), sodium fluoride (NaF), potassium fluoride (KF), barium fluoride (BaF2), cerium fluoride (CeF2), lanthanum fluoride (LaF3), and sodium aluminum hexafluoride (Na3AlF6). The fluorine source is not limited to a solid, and may be, for example, fluorine (F2), carbon fluoride, sulfur fluoride, oxygen fluoride (OF2, O2F2, O3F2, O4F2, O2F), etc., which may be mixed into the atmosphere in the heating step described below. A mixture of multiple fluorine sources may also be used. Among them, lithium fluoride is preferable because it has a relatively low melting point of 848°C and is easily melted in the annealing step described below.
[0265] As the chlorine source, for example, lithium chloride, magnesium chloride, etc. can be used.
[0266] As the magnesium source, for example, magnesium fluoride, magnesium oxide, magnesium hydroxide, magnesium carbonate, etc. can be used.
[0267] Examples of the lithium source include lithium fluoride and lithium carbonate. In other words, lithium fluoride can be used as both a lithium source and a fluorine source. Magnesium fluoride can be used as both a fluorine source and a magnesium source.
[0268] In this embodiment, lithium fluoride LiF is prepared as the fluorine source, and magnesium fluoride MgF2 is prepared as the fluorine source and magnesium source. When lithium fluoride LiF and magnesium fluoride MgF2 are mixed at a molar ratio of about LiF:MgF2=65:35, the effect of lowering the melting point is maximized (Non-Patent Document 4). On the other hand, if the amount of lithium fluoride is large, there is a concern that the lithium becomes excessive and the cycle characteristics deteriorate. Therefore, the molar ratio of lithium fluoride LiF and magnesium fluoride MgF2 is preferably LiF:MgF2=x:1 (0≦x≦1.9), more preferably LiF:MgF2=x:1 (0.1≦x≦0.5), and even more preferably LiF:MgF2=x:1 (near x=0.33). In this specification, etc., "near" refers to a value that is greater than 0.9 times and less than 1.1 times the value.
[0269] In addition, when the next mixing and grinding process is performed in a wet manner, a solvent is prepared. As the solvent, a ketone such as acetone, an alcohol such as ethanol or isopropanol, an ether such as diethyl ether, dioxane, acetonitrile, N-methyl-2-pyrrolidone (NMP), etc. can be used. It is more preferable to use an aprotic solvent that is less likely to react with lithium. In this embodiment, acetone is used.
[0270] <Step S22> Next, in step S22, the materials of the mixture 902 are mixed and pulverized. Mixing can be performed in a dry or wet manner, but the wet method is preferred because it allows for finer pulverization. For example, a ball mill, a bead mill, etc. can be used for mixing. When using a ball mill, it is preferable to use zirconia balls, for example, as the pulverization media. It is preferable to thoroughly perform this mixing and pulverization process to finely pulverize the mixture 902.
[0271] <Step S23> Next, in step S23, the mixed and crushed materials are collected to obtain a mixture 902.
[0272] The mixture 902 preferably has a D50 (median diameter) of, for example, 600 nm to 20 μm, more preferably 1 μm to 10 μm. Alternatively, 600 nm to 10 μm is preferable. Alternatively, 1 μm to 20 μm is preferable. If the mixture 902 is finely pulverized in this way, when it is mixed with a composite oxide having lithium, a transition metal M, and oxygen in a later process, the mixture 902 can be easily attached uniformly to the surface of the composite oxide particles. If the mixture 902 is uniformly attached to the surface of the composite oxide particles, it is preferable because it is easy to distribute halogen and magnesium thoroughly in the surface vicinity region of the composite oxide particles after heating. If there is a region in the surface vicinity region that does not contain halogen and magnesium, it may be difficult to form a pseudo-spinel type crystal structure described later in the charged state.
[0273] <Step S41> Next, in step S41, the LiMO2 obtained in step S14 is mixed with the mixture 902. The ratio of the number of transition metal atoms M in the composite oxide having lithium, transition metal, and oxygen to the number of magnesium atoms Mg in the mixture 902 is preferably M:Mg=100:y (0.1≦y≦6), and more preferably M:Mg=100:y (0.3≦y≦3).
[0274] The mixing in step S41 is preferably performed under milder conditions than those in step S12 in order not to destroy the composite oxide particles. For example, the mixing is preferably performed under conditions of a lower rotation speed or shorter time than those in step S12. It can also be said that the dry method is less likely to destroy the particles than the wet method. For example, a ball mill, a bead mill, etc. can be used for mixing. When using a ball mill, it is preferable to use zirconia balls as the grinding media, for example.
[0275] In addition, aluminum and nickel may be further mixed in the mixing in step S41. Aluminum is trivalent and has a strong bond with oxygen. Therefore, if aluminum is contained as an impurity (or an added element), it is possible to suppress changes in the crystal structure when it enters the lithium site. Therefore, it is possible to obtain a positive electrode active material whose crystal structure is not easily broken even after repeated charging and discharging. Nickel may also increase the capacity per weight and per volume. The nickel source and the aluminum source can be mixed in step S42 at the same time as the mixture 902. Nickel oxide, nickel hydroxide, etc. can be used as the nickel source. Aluminum oxide, aluminum hydroxide, etc. can be used as the aluminum source. This method is preferable because it is highly productive since the number of times the material is placed in the heating furnace is small.
[0276] <Step S42> Next, in step S42, the mixed materials are collected to obtain a mixture 903.
[0277] In this embodiment, a method of adding a mixture of lithium fluoride and magnesium fluoride to lithium cobalt oxide containing few impurities (or added elements) is described, but one embodiment of the present invention is not limited to this. Instead of the mixture 903 in step S42, a starting material of lithium cobalt oxide may be used to which a magnesium source, a fluorine source, and the like are added and then fired. In this case, there is no need to separate the steps S11 to S14 from the steps S21 to S23, and therefore the process is simple and has high productivity.
[0278] Alternatively, lithium cobalt oxide to which magnesium and fluorine have been added in advance may be used. If lithium cobalt oxide to which magnesium and fluorine have been added is used, the steps up to step S32 can be omitted, which is simpler.
[0279] Furthermore, a magnesium source and a fluorine source may be further added to lithium cobalt oxide to which magnesium and fluorine have already been added.
[0280] <Step S43> Next, in step S43, the mixture 903 is heated in an atmosphere containing oxygen. It is more preferable that the heating is performed in a manner that suppresses adhesion so that particles of the mixture 903 do not adhere to each other. During this heating, some element sources, for example LiF, which can be a fluorine source and a lithium source, are lighter than oxygen, so that LiF may volatilize due to heating and the amount of LiF in the mixture 903 may decrease. Therefore, when heating the mixture 903, it is preferable to control the partial pressure of fluorine or fluoride in the atmosphere to an appropriate range. For example, there is a method of putting the mixture 903 in and then covering the heating crucible before and after this heating. This process is the second heating, and may be called annealing to distinguish it from the previous heating process.
[0281] Examples of heating that has an effect of suppressing adhesion include heating while stirring the mixture 903, heating while vibrating a container containing the mixture 903, and the like.
[0282] The temperature of the second heating in step S43 must be equal to or higher than the temperature at which the reaction between LiMO2 and the mixture 902 proceeds. The temperature at which the reaction proceeds may be any temperature at which mutual diffusion of elements contained in LiMO2 and the mixture 902 occurs. Therefore, the temperature may be lower than the melting temperature of these materials. For example, in the case of oxides, the melting temperature T m 0.757 times (Tammann temperature T d ) solid-state diffusion occurs. Therefore, for example, a temperature of 500°C or higher is sufficient.
[0283] However, the reaction proceeds more easily if the temperature is equal to or higher than the temperature at which at least a part of the mixture 903 melts. Therefore, the temperature of the second heating is preferably equal to or higher than the eutectic point of the mixture 902. When the mixture 902 contains LiF and MgF2, the eutectic point of LiF and MgF2 is around 742°C, so it is preferable to set the temperature of step S43 to 742°C or higher.
[0284] In addition, a mixture 903 in which LiCoO2:LiF:MgF2 is mixed at a molar ratio of 100:0.33:1 shows an endothermic peak at about 830° C. in differential scanning calorimetry (DSC measurement). Therefore, the second heating temperature is more preferably 830° C. or higher.
[0285] A higher annealing temperature is preferable because the reaction proceeds more easily, the annealing time is shorter, and the productivity is high.
[0286] However, the temperature of the second heating must be below the decomposition temperature of LiMO2 (1130°C for LiCoO2). At temperatures close to the decomposition temperature, there is concern that LiMO2 may decompose, albeit in a small amount. Therefore, the temperature of the second heating is preferably 1130°C or lower, more preferably 1000°C or lower, even more preferably 950°C or lower, and even more preferably 900°C or lower.
[0287] Therefore, the temperature of the second heating is preferably 500°C to 1130°C, more preferably 500°C to 1000°C, even more preferably 500°C to 950°C, and even more preferably 500°C to 900°C. Also, it is preferably 742°C to 1130°C, more preferably 742°C to 1000°C, even more preferably 742°C to 950°C, and even more preferably 742°C to 900°C. Also, it is preferably 830°C to 1130°C, more preferably 830°C to 1000°C, even more preferably 830°C to 950°C, and even more preferably 830°C to 900°C.
[0288] Furthermore, when the mixture 903 is heated, it is preferable to control the partial pressure of fluorine or fluoride in the atmosphere within an appropriate range.
[0289] In the manufacturing method described in this embodiment, some materials, for example LiF, which is a fluorine source, function as a flux. This function allows the temperature of the second heating to be lowered to the decomposition temperature of LiMO2 or lower, for example, to 742°C to 950°C, and additives such as magnesium can be distributed in the surface vicinity region, making it possible to manufacture a positive electrode active material with good characteristics.
[0290] However, because LiF is lighter than oxygen, when LiF volatilizes due to heating, the amount of LiF in mixture 903 decreases. This weakens its function as a flux. Therefore, it is necessary to heat while suppressing the volatilization of LiF. Even if LiF is not used as a fluorine source, Li and F on the LiMO2 surface may react to produce LiF, which may then volatilize. Therefore, even if a fluoride with a higher melting point than LiF is used, it is still necessary to suppress volatilization in the same way.
[0291] Therefore, it is preferable to heat the mixture 903 in an atmosphere containing LiF, that is, to heat the mixture 903 in a state where the partial pressure of LiF is high in the heating furnace. By such heating, the volatilization of LiF in the mixture 903 can be suppressed.
[0292] The second heating is preferably performed for an appropriate time. The appropriate second heating time varies depending on conditions such as the temperature of the second heating, the size and composition of the LiMO2 particles in step S14, etc. If the particles are small, a lower temperature or a shorter time may be more preferable than if the particles are large.
[0293] For example, when the average particle size (D50) of the particles in step S14 is about 12 μm, the temperature of the second heating is preferably, for example, 600° C. or more and 950° C. or less. The time of the second heating is preferably, for example, 3 hours or more, more preferably 10 hours or more, and even more preferably 60 hours or more.
[0294] On the other hand, when the average particle size (D50) of the particles in step S24 is about 5 μm, the second heating temperature is preferably, for example, from 600° C. to 950° C. The second heating time is preferably, for example, from 1 hour to 10 hours, and more preferably about 2 hours.
[0295] The temperature-lowering time after the second heating is preferably, for example, 10 hours or more and 50 hours or less.
[0296] The second heating may be carried out either continuously or batchwise.
[0297] <Step S51> In step S51, an additive element source is prepared. In this embodiment, the additive element for forming the electric field buffer region 103 is one or more selected from hafnium, zirconium, yttrium, barium, titanium, lead, scandium, strontium, bismuth, and tantalum.
[0298] In this embodiment, an example is shown in which titanium is used and the sol-gel method is applied. When the sol-gel method is applied, a solvent to be used in the sol-gel method is prepared. In the case of titanium, for example, the number of cobalt atoms in lithium cobalt oxide is 1, and the concentration of titanium in the metal source is 0.001 times or more and 0.02 times or less.
[0299] As an example, a sol-gel method is applied, and titanium (IV) tetraisopropoxide (TTIP) is used as the metal source and isopropanol is used as the solvent.
[0300] Next, titanium alkoxide is dissolved in alcohol, and lithium cobalt oxide particles are further mixed therein (Step S61 in FIG. 6).
[0301] The required amount of metal alkoxide varies depending on the particle size of lithium cobalt oxide. For example, when titanium isopropoxide is used and the particle size (D50) of lithium cobalt oxide is about 20 μm, it is preferable to add titanium isopropoxide so that the concentration of titanium in the lithium cobalt oxide is 0.001 to 0.02 times the number of cobalt atoms in the lithium cobalt oxide.
[0302] Next, the mixture of the alcohol solution of the metal alkoxide and the lithium cobalt oxide particles is stirred in an atmosphere containing water vapor. Stirring can be performed, for example, with a magnetic stirrer. The stirring time may be long enough for the water in the atmosphere and the metal alkoxide to undergo hydrolysis and polycondensation reactions, and may be performed, for example, for 4 hours under conditions of 25°C and 90% RH (relative humidity). Stirring may also be performed in an atmosphere without humidity and temperature control, for example, in the air atmosphere in a draft chamber. In such cases, it is preferable to use a longer stirring time, for example, 12 hours or more at room temperature.
[0303] By gradually taking in water vapor from the atmosphere and gradually volatilizing the alcohol, the water and metal alkoxide react, allowing the sol-gel reaction to proceed gently. By reacting the metal alkoxide with water at room temperature, the sol-gel reaction can proceed more gently than when, for example, heating is performed at a temperature exceeding the boiling point of the solvent alcohol.
[0304] Water may also be added actively. If a gentle reaction is desired, the reaction time may be controlled by gradually adding water diluted with alcohol, reducing the amount of alcohol in the bath, adding a stabilizer, or the like. By gently advancing the sol-gel reaction, a coating film of uniform thickness and good quality can be formed. However, the coating film obtained is not necessarily uniform and may be scattered. In this embodiment, the electric field relaxation regions 103 are intentionally scattered to form projecting portions scattered on the surface of the positive electrode active material 100.
[0305] The precipitate is collected from the mixed solution after the above treatment. The collection method can be filtration, centrifugation, evaporation to dryness, or the like. The precipitate can be washed with the same alcohol as the solvent in which the metal alkoxide was dissolved. When evaporation to dryness is used, it is not necessary to separate the solvent and the precipitate in this step, and the precipitate can be collected, for example, in the drying step of the next step (step S44).
[0306] Next, the collected residue is dried to obtain a mixture 904 (Step S62 in FIG. 6). The drying process can be performed, for example, by vacuum or ventilation drying at 80° C. for 1 hour or more and 4 hours or less.
[0307] In addition, when the sol-gel method is not used, the mixture 903 may be formed into a film by a sputtering method or a deposition method. In that case, the mixture 904 can be obtained after the film is formed. In addition, the stirring ball and the mixture 903 can be heated while being stirred, or the stirring ball and the container containing the mixture 903 can be heated while being vibrated. As the material of the stirring ball, an additive element for forming the electric field relaxation region 103 is used, and zirconium oxide, titanium oxide, etc. are preferable. Heating by a rotary kiln can be performed while stirring in either the continuous type or the batch type, and is preferable as an adhesion suppression annealing. The continuous type is preferable because of its high productivity. The batch type is preferable because it is easy to control the atmosphere. When heating by a roller hearth kiln, it is preferable to vibrate the container containing the mixture 903 during heating. The roller hearth kiln is a continuous type, and is therefore preferable because of its high productivity. In that case, the mixture 904 can be obtained after stirring.
[0308] <Step S63> Next, the resulting mixture is heated (Step S63 in FIG. 6).
[0309] The heating time is preferably from 1 hour to 80 hours within the heating temperature range, and from 1 hour to 20 hours is more preferable in terms of productivity.
[0310] The heating temperature is less than 1000°C, preferably 700°C to 950°C, and more preferably about 850°C.
[0311] Moreover, the heating is preferably carried out in an atmosphere containing oxygen.
[0312] In this embodiment, the heating temperature is set to 850° C. and held for 2 hours, the temperature increase rate is set to 200° C. / h, and the oxygen flow rate is set to 10 L / min.
[0313] The heating temperature in step S63 is preferably lower than the heating temperature in step S43.
[0314] <Step S66> Next, the cooled particles are collected. Furthermore, the particles are preferably sieved. Through the above steps, the positive electrode active material 100 of one embodiment of the present invention can be produced (Step S66 in FIG. 6).
[0315] In addition, the conditions (temperature and time) of the third heating may be changed and the Nth (N>3) heating, cooling, and recovery may be repeated n (n>2) times.
[0316] <Surface SEM image>
[0317] FIG. 7(A) is an SEM image of the surface of the sample of this embodiment.
[0318] The sample of this embodiment uses commercially available lithium cobalt oxide (Cellseed C-10N, manufactured by Nippon Chemical Industry Co., Ltd.) as the starting material. Lithium fluoride, magnesium fluoride, nickel hydroxide, and aluminum hydroxide were added to this starting material by the solid-phase method, and titanium was further added by the sol-gel method. When the number of atoms of cobalt is 100, the molecular weight of lithium fluoride was 0.33, the molecular weight of magnesium fluoride was 1, the atomic weight of nickel was 0.5, and the atomic weight of aluminum was 0.5. In the solid-phase method, the heating conditions were 900°C and 10 hours, and after heating, the adhesion of the particles was broken by hitting with a pestle. This heating and breaking process was repeated three times in total. The heating temperature in the sol-gel method was 850°C, and the heating time was 2 hours, resulting in 100 positive electrode active materials.
[0319] It was observed that the positive electrode active material had many protrusions on the surface of the main body. Figure 7(B) shows a cross-sectional STEM image of the white dotted line part in Figure 7(A). Figure 7(C) shows an enlarged cross-sectional STEM image of the protrusions in the white dotted line part in Figure 7(B).
[0320] The EDX mapping images of the white dotted square area in Figure 7(C) are shown in Figures 8(A) to 8(G). Figure 8(A) is a mapping image for oxygen, Figure 8(B) is a mapping image for fluorine, Figure 8(C) is a mapping image for magnesium, Figure 8(D) is a mapping image for titanium, Figure 8(E) is a mapping image for nickel, Figure 8(F) is aluminium, and Figure 8(G) is a mapping image for cobalt.
[0321] 8(A) to 8(G), it was confirmed that the convex portion had a high-fluorine concentration region in which the fluorine concentration was higher than that of the main body and the high-metal-element concentration region. It was also confirmed that the convex portion had a high-metal-element concentration region in which the concentrations of magnesium, titanium, and nickel were higher than that of the main body and the high-fluorine concentration region. This high-metal-element concentration region can also be called an alloy region.
[0322] The nickel mapping image in Figure 8(E) confirmed the presence of a high nickel concentration region in part of the body. It is presumed that the excess magnesium, titanium, and nickel contained in the positive electrode active material are agglomerated in the high metal element concentration region. In particular, nickel is attracted to the high metal element concentration region from inside the body, and the high nickel concentration region present in part of the body can be called an alloy region, and it is suggested that it may be a trace of this.
[0323] On the other hand, the aluminum concentration near the surface of the body was higher than in the interior or on the protruding parts. It was confirmed that aluminum did not aggregate in the high metal element concentration regions, but remained near the surface.
[0324] 7B, which is a convex portion, corresponds to electric field relaxation region 103 in FIG. 1A. In the production method of this embodiment, positive electrode active material 100 shown in FIG. 1A is obtained, but positive electrode active material 104 shown in FIG. 1B or positive electrode active material 105 shown in FIG. 1C can also be obtained by selecting an additive element source and appropriately changing the conditions in the production flow shown in FIG. 6.
[0325] In addition, the production flow shown in Fig. 6 is merely an example and is not particularly limited. For example, in order to reduce the number of heating steps and the manufacturing cost, LiMO2 and a plurality of additive element sources may be mixed in step S14, and the positive electrode active material 100 may be obtained by the second heating in step 43 without performing the third heating.
[0326] This embodiment mode can be freely combined with other embodiment modes.
[0327] (Embodiment 4) In this embodiment mode, examples of a plurality of types of shapes of secondary batteries each having a positive electrode or a negative electrode manufactured by the manufacturing method described in the previous embodiment will be described.
[0328] [Coin-type secondary battery] An example of a coin-type secondary battery will be described. Fig. 14(A) is an exploded perspective view of a coin-type (single-layer flat) secondary battery, Fig. 14(B) is an external view, and Fig. 14(C) is a cross-sectional view thereof. Coin-type secondary batteries are mainly used in small electronic devices.
[0329] In order to make it easier to understand, Fig. 14(A) is a schematic diagram showing the overlapping of components (upper and lower relationships and positional relationships). Therefore, Fig. 14(A) and Fig. 14(B) are not completely corresponding views.
[0330] In Fig. 14(A), a positive electrode 304, a separator 310, a negative electrode 307, a spacer 322, and a washer 312 are stacked. These are sealed by a negative electrode can 302 and a positive electrode can 301. Note that a gasket for sealing is not shown in Fig. 14(A). The spacer 322 and the washer 312 are used to protect the inside or to fix the position inside the can when the positive electrode can 301 and the negative electrode can 302 are crimped together. The spacer 322 and the washer 312 are made of stainless steel or an insulating material.
[0331] A laminated structure in which a positive electrode active material layer 306 is formed on a positive electrode current collector 305 is used as a positive electrode 304 .
[0332] In order to prevent a short circuit between the positive electrode and the negative electrode, a separator 310 and a ring-shaped insulator 313 are arranged so as to cover the side and top surfaces of the positive electrode 304. The separator 310 has a larger planar area than the positive electrode 304.
[0333] FIG. 14(B) is a perspective view of the completed coin-type secondary battery.
[0334] In the coin-type secondary battery 300, a positive electrode can 301 also serving as a positive electrode terminal and a negative electrode can 302 also serving as a negative electrode terminal are insulated and sealed by a gasket 303 made of polypropylene or the like. The positive electrode 304 is formed of a positive electrode current collector 305 and a positive electrode active material layer 306 provided in contact with the positive electrode current collector. The negative electrode 307 is formed of a negative electrode current collector 308 and a negative electrode active material layer 309 provided in contact with the negative electrode current collector. The negative electrode 307 is not limited to a laminated structure, and may be a lithium metal foil or a lithium-aluminum alloy foil.
[0335] In addition, the positive electrode 304 and the negative electrode 307 used in the coin-type secondary battery 300 each need only have an active material layer formed on one side.
[0336] Metals such as nickel, aluminum, and titanium that are corrosion-resistant to the electrolyte, or alloys of these metals and other metals (e.g., stainless steel, etc.) can be used for the positive electrode can 301 and the negative electrode can 302. In order to prevent corrosion by the electrolyte, it is preferable to coat them with nickel, aluminum, etc. The positive electrode can 301 is electrically connected to the positive electrode 304, and the negative electrode can 302 is electrically connected to the negative electrode 307.
[0337] These negative electrode 307, positive electrode 304 and separator 310 are immersed in an electrolyte, and as shown in FIG. 9(C), positive electrode can 301 is placed down, and positive electrode 304, separator 310, negative electrode 307 and negative electrode can 302 are stacked in this order, and positive electrode can 301 and negative electrode can 302 are crimped together via gasket 303, to produce coin-type secondary battery 300.
[0338] By using the positive electrode active material 100 obtained in the first embodiment for the positive electrode 304, it is possible to obtain a coin-type secondary battery 300 having a high capacity, a high charge / discharge capacity, and excellent cycle characteristics. Note that when a secondary battery is formed between the negative electrode 307 and the positive electrode 304, the separator 310 may not be necessary.
[0339] [Cylindrical secondary battery] An example of a cylindrical secondary battery will be described with reference to Fig. 15(A). As shown in Fig. 15(A), a cylindrical secondary battery 616 has a positive electrode cap (battery lid) 601 on the top surface, and a battery can (external can) 602 on the side and bottom surfaces. The positive electrode cap 601 and the battery can (external can) 602 are insulated by a gasket (insulating packing) 610.
[0340] Fig. 15(B) is a schematic diagram showing a cross section of a cylindrical secondary battery. The cylindrical secondary battery shown in Fig. 15(B) has a positive electrode cap (battery lid) 601 on the top surface, and a battery can (external can) 602 on the side and bottom surfaces. The positive electrode cap and the battery can (external can) 602 are insulated by a gasket (insulating packing) 610.
[0341] Inside a hollow cylindrical battery can 602, a battery element is provided in which a strip-shaped positive electrode 604 and a negative electrode 606 are wound with a separator 605 sandwiched therebetween. Although not shown, the battery element is wound around a center pin. One end of the battery can 602 is closed and the other end is open. For the battery can 602, metals such as nickel, aluminum, and titanium that are resistant to corrosion by electrolytes, or alloys of these or alloys of these with other metals (e.g., stainless steel, etc.) can be used. In addition, in order to prevent corrosion by the electrolyte, it is preferable to coat the battery can 602 with nickel, aluminum, or the like. Inside the battery can 602, the battery element in which the positive electrode, the negative electrode, and the separator are wound is sandwiched between a pair of opposing insulating plates 608 and 609. In addition, a nonaqueous electrolyte (not shown) is injected inside the battery can 602 in which the battery element is provided. The nonaqueous electrolyte can be the same as that of a coin-type secondary battery.
[0342] Since the positive and negative electrodes used in a cylindrical storage battery are wound, it is preferable to form active materials on both sides of the current collector.
[0343] By using the positive electrode active material 100 obtained in Embodiment 1 for the positive electrode 604, a cylindrical secondary battery 616 having a high capacity, a high charge / discharge capacity, and excellent cycle characteristics can be obtained.
[0344] A positive electrode terminal (positive electrode current collector lead) 603 is connected to the positive electrode 604, and a negative electrode terminal (negative electrode current collector lead) 607 is connected to the negative electrode 606. Both the positive electrode terminal 603 and the negative electrode terminal 607 can be made of a metal material such as aluminum. The positive electrode terminal 603 is resistance-welded to a safety valve mechanism 613, and the negative electrode terminal 607 is resistance-welded to the bottom of the battery can 602. The safety valve mechanism 613 is electrically connected to the positive electrode cap 601 via a PTC element (Positive Temperature Coefficient) 611. The safety valve mechanism 613 cuts off the electrical connection between the positive electrode cap 601 and the positive electrode 604 when the increase in the internal pressure of the battery exceeds a predetermined threshold value. The PTC element 611 is a thermosensitive resistor element whose resistance increases when the temperature increases, and the increase in resistance limits the amount of current to prevent abnormal heat generation. The PTC element can be made of barium titanate (BaTiO3)-based semiconductor ceramics or the like.
[0345] 15C shows an example of a power storage system 615. The power storage system 615 has a plurality of secondary batteries 616. A positive electrode of each secondary battery is in contact with and electrically connected to a conductor 624 separated by an insulator 625. The conductor 624 is electrically connected to a control circuit 620 via a wiring 623. A negative electrode of each secondary battery is electrically connected to the control circuit 620 via a wiring 626. As the control circuit 620, a charge / discharge control circuit that performs charging / discharging and the like or a protection circuit that prevents overcharging or overdischarging can be used.
[0346] 15(D) shows an example of a power storage system 615. The power storage system 615 has a plurality of secondary batteries 616, and the plurality of secondary batteries 616 are sandwiched between a conductive plate 628 and a conductive plate 614. The plurality of secondary batteries 616 are electrically connected to the conductive plate 628 and the conductive plate 614 by wiring 627. The plurality of secondary batteries 616 may be connected in parallel, may be connected in series, or may be connected in parallel and then further connected in series. By configuring the power storage system 615 having the plurality of secondary batteries 616, it is possible to extract a large amount of power.
[0347] A plurality of secondary batteries 616 may be connected in parallel and then further connected in series.
[0348] A temperature control device may be provided between the multiple secondary batteries 616. When the secondary batteries 616 are overheated, they can be cooled by the temperature control device, and when the secondary batteries 616 are too cold, they can be heated by the temperature control device. This makes the performance of the power storage system 615 less susceptible to the effect of the outside air temperature.
[0349] 15(D), the power storage system 615 is electrically connected to a control circuit 620 via wiring 621 and wiring 622. The wiring 621 is electrically connected to the positive electrodes of the multiple secondary batteries 600 via a conductive plate 628, and the wiring 622 is electrically connected to the negative electrodes of the multiple secondary batteries 600 via a conductive plate 614.
[0350] [Other examples of secondary battery structures] An example of the structure of the secondary battery will be described with reference to FIGS.
[0351] A secondary battery 913 shown in FIG. 16A has a wound body 950 in which terminals 951 and 952 are provided inside a housing 930. The wound body 950 is immersed in an electrolyte inside the housing 930. The terminal 952 contacts the housing 930, and the terminal 951 does not contact the housing 930 by using an insulating material or the like. Note that in FIG. 16A, the housing 930 is shown separated for convenience, but in reality, the wound body 950 is covered by the housing 930, and the terminals 951 and 952 extend outside the housing 930. The housing 930 can be made of a metal material (e.g., aluminum) or a resin material.
[0352] As shown in Fig. 16(B), the housing 930 shown in Fig. 16(A) may be formed using a plurality of materials. For example, a secondary battery 913 shown in Fig. 16(B) has a housing 930a and a housing 930b bonded together, and a wound body 950 is provided in a region surrounded by the housing 930a and the housing 930b.
[0353] The housing 930a can be made of an insulating material such as organic resin. In particular, by using a material such as organic resin on the surface on which the antenna is formed, it is possible to suppress shielding of the electric field by the secondary battery 913. Note that if the shielding of the electric field by the housing 930a is small, the antenna may be provided inside the housing 930a. The housing 930b can be made of, for example, a metal material.
[0354] 16(C) shows the structure of the wound body 950. The wound body 950 has a negative electrode 931, a positive electrode 932, and a separator 933. The wound body 950 is a wound body in which the negative electrode 931 and the positive electrode 932 are stacked with the separator 933 sandwiched therebetween, and the laminated sheet is wound. Note that the stack of the negative electrode 931, the positive electrode 932, and the separator 933 may be stacked a plurality of times.
[0355] Alternatively, a secondary battery 913 may have a wound body 950a as shown in Fig. 17. A wound body 950a shown in Fig. 17(A) has a negative electrode 931, a positive electrode 932, and a separator 933. The negative electrode 931 has a negative electrode active material layer 931a. The positive electrode 932 has a positive electrode active material layer 932a.
[0356] By using the positive electrode active material 100 obtained in Embodiment 1 for the positive electrode 932, the secondary battery 913 can have a high capacity, a high charge / discharge capacity, and excellent cycle characteristics.
[0357] The separator 933 has a width wider than the negative electrode active material layer 931a and the positive electrode active material layer 932a, and is wound so as to overlap the negative electrode active material layer 931a and the positive electrode active material layer 932a. From the viewpoint of safety, it is preferable that the width of the negative electrode active material layer 931a is wider than that of the positive electrode active material layer 932a. Moreover, a wound body 950a having such a shape is preferable because of its high safety and productivity.
[0358] 17B, the negative electrode 931 is electrically connected to a terminal 951. The terminal 951 is electrically connected to a terminal 911a. The positive electrode 932 is electrically connected to a terminal 952. The terminal 952 is electrically connected to a terminal 911b.
[0359] 17(C), the wound body 950a and the electrolyte are covered with the housing 930 to form the secondary battery 913. It is preferable to provide a safety valve, an overcurrent protection element, and the like in the housing 930. The safety valve is a valve that opens when the inside of the housing 930 reaches a predetermined internal pressure in order to prevent the battery from exploding.
[0360] As shown in Fig. 17(B), the secondary battery 913 may have a plurality of wound bodies 950a. By using a plurality of wound bodies 950a, the secondary battery 913 can have a larger charge / discharge capacity. For other elements of the secondary battery 913 shown in Figs. 17(A) and (B), the description of the secondary battery 913 shown in Figs. 16(A) to (C) can be referred to.
[0361] <Laminated secondary battery> Next, an example of an external view of a laminated secondary battery is shown in Fig. 18(A) and Fig. 18(B). Fig. 18(A) and Fig. 18(B) have a positive electrode 503, a negative electrode 506, a separator 507, an exterior body 509, a positive electrode lead electrode 510, and a negative electrode lead electrode 511.
[0362] FIG. 19(A) shows an external view of a positive electrode 503 and a negative electrode 506. The positive electrode 503 has a positive electrode current collector 501, and a positive electrode active material layer 502 is formed on the surface of the positive electrode current collector 501. The positive electrode 503 has a region where the positive electrode current collector 501 is partially exposed (hereinafter referred to as a tab region). The negative electrode 506 has a negative electrode current collector 504, and a negative electrode active material layer 505 is formed on the surface of the negative electrode current collector 504. The negative electrode 506 has a region where the negative electrode current collector 504 is partially exposed, that is, a tab region. The areas and shapes of the tab regions of the positive electrode and negative electrode are not limited to the example shown in FIG. 19(A).
[0363] <Method of manufacturing laminated secondary battery> Here, an example of a method for manufacturing the laminate type secondary battery whose external view is shown in FIG. 18(A) will be described with reference to FIGS. 19(B) and 19(C).
[0364] First, the negative electrode 506, the separator 507, and the positive electrode 503 are laminated. FIG. 19(B) shows the laminated negative electrode 506, the separator 507, and the positive electrode 503. Here, an example is shown in which five pairs of negative electrodes and four pairs of positive electrodes are used. It can also be called a laminate consisting of a negative electrode, a separator, and a positive electrode. Next, the tab regions of the positive electrodes 503 are bonded to each other, and the positive electrode lead electrode 510 is bonded to the tab region of the outermost positive electrode. For example, ultrasonic welding or the like may be used for the bonding. Similarly, the tab regions of the negative electrodes 506 are bonded to each other, and the negative electrode lead electrode 511 is bonded to the tab region of the outermost negative electrode.
[0365] Next, the negative electrode 506 , the separator 507 and the positive electrode 503 are placed on the exterior body 509 .
[0366] Next, as shown in Fig. 19(C), exterior body 509 is folded at the portion indicated by the dashed line. After that, the outer periphery of exterior body 509 is joined. For the joining, for example, thermocompression bonding or the like may be used. At this time, a region (hereinafter referred to as an inlet) that is not joined is provided in a part (or one side) of exterior body 509 so that electrolyte 508 can be introduced later.
[0367] Next, electrolyte 508 (not shown) is introduced into the inside of exterior body 509 through an inlet provided in exterior body 509. The introduction of electrolyte 508 is preferably performed under a reduced pressure atmosphere or an inert atmosphere. Finally, the inlet is joined. In this manner, laminate type secondary battery 500 can be produced.
[0368] By using the positive electrode active material 100 obtained in the first embodiment for the positive electrode 503, it is possible to obtain the secondary battery 500 having a high capacity, a high charge / discharge capacity, and excellent cycle characteristics.
[0369] [Example of a battery pack] An example of a secondary battery pack according to one embodiment of the present invention which can be wirelessly charged using an antenna will be described with reference to FIG.
[0370] FIG. 20(A) is a diagram showing the appearance of secondary battery pack 531, which has a thin rectangular parallelepiped shape (also called a thick flat plate shape). FIG. 20(B) is a diagram explaining the configuration of secondary battery pack 531. Secondary battery pack 531 has circuit board 540 and secondary battery 513. Label 529 is attached to secondary battery 513. Circuit board 540 is fixed by sticker 515. Secondary battery pack 531 also has antenna 517.
[0371] The inside of the secondary battery 513 may have a structure having a wound body or a structure having a laminated body.
[0372] 20(B), the secondary battery pack 531 has a control circuit 590 on a circuit board 540. The circuit board 540 is electrically connected to a terminal 514. The circuit board 540 is also electrically connected to an antenna 517, one 551 of a positive electrode lead and a negative electrode lead of a secondary battery 513, and the other 552 of a positive electrode lead and a negative electrode lead of the secondary battery 513.
[0373] 20C, a circuit system 590a provided on a circuit board 540 and a circuit system 590b electrically connected to the circuit board 540 via a terminal 514 may be provided.
[0374] The antenna 517 is not limited to a coil shape, and may be, for example, a wire shape or a plate shape. In addition, antennas such as a planar antenna, an aperture antenna, a traveling wave antenna, an EH antenna, a magnetic field antenna, and a dielectric antenna may be used. Alternatively, the antenna 517 may be a flat conductor. This flat conductor can function as one of the conductors for electric field coupling. In other words, the antenna 517 may function as one of the two conductors of a capacitor. This allows power to be exchanged not only by electromagnetic fields and magnetic fields, but also by electric fields.
[0375] The secondary battery pack 531 has a layer 519 between the antenna 517 and the secondary battery 513. The layer 519 has a function of, for example, shielding an electromagnetic field caused by the secondary battery 513. The layer 519 can be made of, for example, a magnetic material.
[0376] This embodiment mode can be freely combined with other embodiment modes.
[0377] (Embodiment 5) In this embodiment, an example of producing an all-solid-state battery using the positive electrode active material 100 obtained in the first embodiment will be described.
[0378] As shown in FIG. 21A, a secondary battery 400 of one embodiment of the present invention includes a positive electrode 410, a solid electrolyte layer 420, and a negative electrode 430.
[0379] The positive electrode 410 has a positive electrode current collector 413 and a positive electrode active material layer 414. The positive electrode active material layer 414 has a positive electrode active material 411 and a solid electrolyte 421. The positive electrode active material 104 obtained in the second embodiment is used for the positive electrode active material 411, and the boundary between the internal region and the shell, which is the electric field relaxation region, is indicated by a dotted line. Note that the positive electrode active material 104 shown in the second embodiment is illustrated here as an example, but is not particularly limited, and the positive electrode active material 100 obtained in the first embodiment or the positive electrode active material 105 shown in the second embodiment can be used instead of the positive electrode active material 104. In addition, two or three different positive electrode active materials may be used in combination in the positive electrode active material layer 414. In addition, the positive electrode active material layer 414 may have a conductive assistant and a binder.
[0380] Solid electrolyte layer 420 has solid electrolyte 421. Solid electrolyte layer 420 is located between positive electrode 410 and negative electrode 430, and is a region that has neither positive electrode active material 411 nor negative electrode active material 431.
[0381] The negative electrode 430 includes a negative electrode current collector 433 and a negative electrode active material layer 434. The negative electrode active material layer 434 includes a negative electrode active material 431 and a solid electrolyte 421. The negative electrode active material layer 434 may include a conductive additive and a binder. When metallic lithium is used for the negative electrode 430, the negative electrode 430 may not include the solid electrolyte 421 as shown in FIG. 21B. When metallic lithium is used for the negative electrode 430, the energy density of the secondary battery 400 can be improved, which is preferable.
[0382] As the solid electrolyte 421 of the solid electrolyte layer 420, for example, a sulfide-based solid electrolyte, an oxide-based solid electrolyte, a halide-based solid electrolyte, or the like can be used.
[0383] Sulfide-based solid electrolytes include thiosilicon-based (Li 10 GeP2S 12 , Li 3.25 Ge 0.25 P 0.75S4, etc.), sulfide glass (70Li2S 30P2S5, 30Li2S 26B2S3 44LiI, 63Li2S 38SiS2 1Li3PO4, 57Li2S 38SiS2 5Li4SiO4, 50Li2S 50GeS2, etc.), sulfide crystallized glass (Li7P3S 11 , Li 3.25 P 0.95 Sulfide-based solid electrolytes have the advantages of being highly conductive, being able to be synthesized at low temperatures, and being relatively soft, making it easy to maintain conductive paths even after charging and discharging.
[0384] Oxide-based solid electrolytes include materials with a perovskite crystal structure (La 2 / 3-x Li 3x TiO3, etc.), materials with NASICON type crystal structure (Li 1-Y Al Y Ti 2-Y (PO4)3, etc.), materials with garnet-type crystal structure (Li7La3Zr2O 12 etc.), materials with LISICON type crystal structure (Li 14 ZnGeO 16 etc.), LLZO(Li7La3Zr2O 12 ), oxide glass (Li3PO4-Li4SiO4, 50Li4SiO4·50Li3BO3, etc.), oxide glass ceramics (Li 1.07 Al 0.69 Ti 1.46 (PO4)3, Li 1.5 Al 0.5 Ge 1.5 (PO4)3, etc. Oxide-based solid electrolytes have the advantage of being stable in the air.
[0385] Halide-based solid electrolytes include LiAlCl4, Li3InBr6, LiF, LiCl, LiBr, LiI, etc. Composite materials in which these halide-based solid electrolytes are filled into the pores of porous aluminum oxide or porous silica can also be used as solid electrolytes.
[0386] Also, different solid electrolytes may be used in combination.
[0387] Among them, Li with NASICON type crystal structure 1+x Al x Ti 2-x Since (PO4)3(0[x[1) (hereinafter, LATP) contains aluminum and titanium, which are elements that may be contained in the positive electrode active material used in the secondary battery 400 of one embodiment of the present invention, a synergistic effect can be expected in improving cycle characteristics, which is preferable. In addition, an improvement in productivity can be expected by reducing the number of steps. In this specification and the like, the NASICON type crystal structure refers to a compound represented by M2(XO4)3 (M: transition metal, X: S, P, As, Mo, W, etc.), which has a structure in which MO6 octahedrons and XO4 tetrahedrons are arranged three-dimensionally with vertices shared.
[0388] [Shapes of exterior body and secondary battery] The exterior body of the secondary battery 400 of one embodiment of the present invention can be made of various materials and has various shapes, but preferably has a function of applying pressure to the positive electrode, the solid electrolyte layer, and the negative electrode.
[0389] For example, Figure 20 shows an example of a cell for evaluating materials for all-solid-state batteries.
[0390] 22(A) is a schematic cross-sectional view of the evaluation cell, which has a lower member 761, an upper member 762, and a fixing screw and a wing nut 764 that fix them, and the electrode plate 753 is pressed by rotating a holding screw 763 to fix the evaluation material. An insulator 766 is provided between the lower member 761 and the upper member 762, which are made of stainless steel. An O-ring 765 is provided between the upper member 762 and the holding screw 763 to seal.
[0391] The evaluation material is placed on electrode plate 751, surrounded by insulating tube 752, and pressed from above by electrode plate 753. An enlarged perspective view of the evaluation material and its periphery is shown in Figure 22(B).
[0392] The evaluation material is an example of a laminate of a positive electrode 750a, a solid electrolyte layer 750b, and a negative electrode 750c, and its cross-sectional view is shown in Fig. 22(C). Note that the same reference numerals are used for the same parts in Figs. 22(A), (B), and (C).
[0393] The electrode plate 751 and the lower member 761 electrically connected to the positive electrode 750a can be said to correspond to a positive electrode terminal. The electrode plate 753 and the upper member 762 electrically connected to the negative electrode 750c can be said to correspond to a negative electrode terminal. The electrical resistance and the like can be measured while applying pressure to the evaluation material via the electrode plate 751 and the electrode plate 753.
[0394] In addition, it is preferable to use a package with excellent airtightness for the exterior body of the secondary battery of one embodiment of the present invention. For example, a ceramic package or a resin package can be used. In addition, it is preferable to seal the exterior body in a sealed atmosphere, for example, in a glove box, while blocking the outside air.
[0395] Fig. 23(A) shows a perspective view of a secondary battery of one embodiment of the present invention having an exterior body and a shape different from those in Fig. 22. The secondary battery in Fig. 23(A) has external electrodes 771 and 772 and is sealed in an exterior body having a plurality of packaging members.
[0396] An example of a cross section cut along the dashed line in Fig. 23(A) is shown in Fig. 23(B). A laminate having a positive electrode 750a, a solid electrolyte layer 750b, and a negative electrode 750c is surrounded and sealed by a package member 770a having an electrode layer 773a on a flat plate, a frame-shaped package member 770b, and a package member 770c having an electrode layer 773b on a flat plate. An insulating material such as a resin material or ceramic can be used for the package members 770a, 770b, and 770c.
[0397] The external electrode 771 is electrically connected to the positive electrode 750a via the electrode layer 773a and functions as a positive electrode terminal, while the external electrode 772 is electrically connected to the negative electrode 750c via the electrode layer 773b and functions as a negative electrode terminal.
[0398] By using the positive electrode active material 100 obtained in the first embodiment, an all-solid-state secondary battery having a high energy density and good output characteristics can be realized.
[0399] This embodiment mode can be used in appropriate combination with other embodiment modes.
[0400] (Embodiment 6) This embodiment is an example different from the cylindrical secondary battery shown in Fig. 15(D) and shows an example of application to an electric vehicle (EV) using Fig. 24(C).
[0401] The electric vehicle is equipped with first batteries 1301a and 1301b as main driving secondary batteries, and a second battery 1311 that supplies power to an inverter 1312 that starts a motor 1304. The second battery 1311 is also called a cranking battery (also called a starter battery). The second battery 1311 only needs to have high output, and does not need to have a large capacity, and the capacity of the second battery 1311 is smaller than that of the first batteries 1301a and 1301b.
[0402] The internal structure of the first battery 1301a may be a wound type shown in FIG. 16(A), FIG. 16(B), FIG. 16(C), or FIG. 17(A), or may be a stacked type shown in FIG. 18(A), FIG. 18(B), FIG. 19(A), FIG. 19(B), or FIG. 19(C). The first battery 1301a may use the all-solid-state battery of the embodiment 5. By using the all-solid-state battery of the embodiment 5 for the first battery 1301a, it is possible to achieve a high capacity, improve safety, and reduce the size and weight.
[0403] In this embodiment, an example is shown in which two first batteries 1301a and 1301b are connected in parallel, but three or more batteries may be connected in parallel. Also, if the first battery 1301a can store sufficient power, the first battery 1301b may not be necessary. By configuring a battery pack having multiple secondary batteries, it is possible to extract large power. The multiple secondary batteries may be connected in parallel, in series, or in series after being connected in parallel. A plurality of secondary batteries is also called a battery pack.
[0404] In addition, in a secondary battery for vehicle use, in order to cut off power from a plurality of secondary batteries, a service plug or circuit breaker capable of cutting off high voltage without using tools is provided in the first battery 1301a.
[0405] The power of the first batteries 1301a and 1301b is mainly used to rotate the motor 1304, but also supplies power to 42V in-vehicle components (such as an electric power steering 1307, a heater 1308, and a defogger 1309) via a DCDC circuit 1306. When a rear motor 1317 is provided for the rear wheels, the first battery 1301a is used to rotate the rear motor 1317.
[0406] In addition, the second battery 1311 supplies power to 14V in-vehicle components (such as an audio system 1313, a power window 1314, and lamps 1315) via the DCDC circuit 1310.
[0407] The first battery 1301a will be described with reference to FIG.
[0408] FIG. 24A shows an example in which nine rectangular secondary batteries 1300 are used as one battery pack 1415. Nine rectangular secondary batteries 1300 are connected in series, one electrode is fixed by a fixing part 1413 made of an insulator, and the other electrode is fixed by a fixing part 1414 made of an insulator. In this embodiment, an example in which the batteries are fixed by the fixing parts 1413 and 1414 is shown, but the batteries may be stored in a battery storage box (also called a housing). Since it is assumed that the vehicle is subjected to vibration or shaking from the outside (such as a road surface), it is preferable to fix a plurality of secondary batteries by the fixing parts 1413 and 1414 or a battery storage box. One electrode is electrically connected to the control circuit part 1320 by a wiring 1421. The other electrode is electrically connected to the control circuit part 1320 by a wiring 1422.
[0409] The control circuit unit 1320 may use a memory circuit including a transistor using an oxide semiconductor. A charge control circuit or a battery control system having a memory circuit including a transistor using an oxide semiconductor may be called a battery operating system (BTOS) or a battery oxide semiconductor. The charge control circuit is a means for controlling a secondary battery stored in the battery pack 1415.
[0410] It is preferable to use a metal oxide that functions as an oxide semiconductor. For example, a metal oxide such as In-M-Zn oxide (wherein element M is one or more selected from aluminum, gallium, yttrium, copper, vanadium, beryllium, boron, titanium, iron, nickel, germanium, zirconium, molybdenum, lanthanum, cerium, neodymium, hafnium, tantalum, tungsten, magnesium, etc.) may be used as the oxide 530. In particular, the In-M-Zn oxide that can be used as the oxide 530 is preferably CAAC-OS (C-Axls Aligned Crystal Oxide Semiconductor) or CAC-OS (Cloud-Aligned Composite Oxide Semiconductor). Alternatively, In-Ga oxide or In-Zn oxide may be used as the oxide 530. CAAC-OS is an oxide semiconductor that has a plurality of crystal regions, and the plurality of crystal regions have c-axes oriented in a specific direction. The specific direction is the thickness direction of the CAAC-OS film, the normal direction of the surface on which the CAAC-OS film is formed, or the normal direction of the surface of the CAAC-OS film. The crystalline region is a region having periodic atomic arrangement. If the atomic arrangement is considered as a lattice arrangement, the crystalline region is also a region with a uniform lattice arrangement. The CAAC-OS has a region in which a plurality of crystalline regions are connected in the ab-plane direction, and the region may have distortion. The distortion refers to a portion in which the direction of the lattice arrangement changes between a region with a uniform lattice arrangement and another region with a uniform lattice arrangement in a region in which a plurality of crystalline regions are connected. That is, the CAAC-OS is an oxide semiconductor that is c-axis oriented and does not have a clear orientation in the ab-plane direction. The CAC-OS is, for example, a material in which elements constituting a metal oxide are unevenly distributed in a size of 0.5 nm to 10 nm, preferably 1 nm to 3 nm, or in the vicinity thereof. In the following, a state in which one or more metal elements are unevenly distributed in a metal oxide and the regions containing the metal elements are mixed in a size of 0.5 nm to 10 nm, preferably 1 nm to 3 nm, or a size close to these sizes, is also referred to as a mosaic or patch shape.
[0411] Furthermore, CAC-OS is a composite metal oxide in which the material is separated into a first region and a second region, forming a mosaic structure, and the first region is distributed throughout the film (hereinafter, also referred to as a cloud structure). In other words, CAC-OS is a composite metal oxide in which the first region and the second region are mixed together.
[0412] Here, the atomic ratios of In, Ga, and Zn to the metal elements constituting the CAC-OS in the In-Ga-Zn oxide are represented as [In], [Ga], and [Zn], respectively. For example, in the CAC-OS in the In-Ga-Zn oxide, the first region is a region where [In] is larger than [In] in the composition of the CAC-OS film. Also, the second region is a region where [Ga] is larger than [Ga] in the composition of the CAC-OS film. Alternatively, for example, the first region is a region where [In] is larger than [In] in the second region and [Ga] is smaller than [Ga] in the second region. Also, the second region is a region where [Ga] is larger than [Ga] in the first region and [In] is smaller than [In] in the first region.
[0413] Specifically, the first region is a region mainly composed of indium oxide, indium zinc oxide, etc., and the second region is a region mainly composed of gallium oxide, gallium zinc oxide, etc. In other words, the first region can be rephrased as a region mainly composed of In, and the second region can be rephrased as a region mainly composed of Ga.
[0414] In addition, there are cases where a clear boundary between the first region and the second region cannot be observed.
[0415] For example, in the case of a CAC-OS of an In-Ga-Zn oxide, EDX mapping obtained using EDX (Energy Dispersive X-ray spectroscopy) has confirmed that the CAC-OS has a structure in which a region mainly composed of In (first region) and a region mainly composed of Ga (second region) are unevenly distributed and mixed.
[0416] When CAC-OS is used in a transistor, the conductivity due to the first region and the insulating property due to the second region act in a complementary manner, giving the CAC-OS a switching function (On / Off function). In other words, CAC-OS has a conductive function in part of the material and an insulating function in other parts of the material, and the material as a whole functions as a semiconductor. By separating the conductive function from the insulating function, it is possible to maximize both functions. Therefore, by using CAC-OS in a transistor, it is possible to achieve a high on-current (I on ), high field effect mobility (μ), and good switching behavior can be achieved.
[0417] Oxide semiconductors have a variety of structures and each structure has different characteristics. The oxide semiconductor of one embodiment of the present invention may include two or more of an amorphous oxide semiconductor, a polycrystalline oxide semiconductor, an a-like OS, a CAC-OS, an nc-OS, and a CAAC-OS.
[0418] In addition, since it can be used in a high-temperature environment, it is preferable that the control circuit unit 1320 uses a transistor using an oxide semiconductor. In order to simplify the process, the control circuit unit 1320 may be formed using a unipolar transistor. The operating ambient temperature of a transistor using an oxide semiconductor in the semiconductor layer is wider than that of single-crystal Si, from -40°C to 150°C, and the change in characteristics is smaller than that of a single crystal even when the secondary battery is heated. The off-current of a transistor using an oxide semiconductor is below the lower limit of measurement regardless of temperature even at 150°C, but the off-current characteristics of a single-crystal Si transistor are highly temperature-dependent. For example, at 150°C, the off-current of a single-crystal Si transistor increases, and the current on / off ratio does not become sufficiently large. The control circuit unit 1320 can improve safety. In addition, a synergistic effect on safety can be obtained by combining the positive electrode active material 100 obtained in the first embodiment with a secondary battery using the positive electrode active material 100 obtained in the first embodiment. The secondary battery using the positive electrode active material 100 obtained in the first embodiment and the control circuit unit 1320 can greatly contribute to the elimination of accidents such as fires caused by secondary batteries.
[0419] The control circuit unit 1320 using a memory circuit including a transistor using an oxide semiconductor can also function as an automatic control device for a secondary battery against ten causes of instability such as micro-short circuit. Functions for eliminating the ten causes of instability include overcharging prevention, overcurrent prevention, overheating control during charging, cell balancing in a battery pack, over-discharging prevention, a remaining capacity meter, automatic control of charging voltage and current amount according to temperature, control of charging current amount according to deterioration degree, detection of abnormal behavior of micro-short circuit, and prediction of abnormality related to micro-short circuit, and the control circuit unit 1320 has at least one of these functions. In addition, the automatic control device for a secondary battery can be made ultra-compact.
[0420] A micro-short circuit refers to a very small short circuit inside a secondary battery, which is not so small that the positive and negative electrodes of the secondary battery are short-circuited and cannot be charged or discharged, but rather refers to a phenomenon in which a small short-circuit current flows through a very small short circuit. Even if it is only in a small location and for a relatively short period of time, a large voltage change occurs, and this abnormal voltage value may affect subsequent estimates.
[0421] One of the causes of micro-short circuits is said to be that multiple charge and discharge cycles cause uneven distribution of the positive electrode active material, resulting in localized current concentration in parts of the positive electrode and negative electrode, causing parts of the separator to stop functioning, or the generation of by-products due to side reactions, resulting in micro-short circuits.
[0422] In addition to detecting micro-shorts, the control circuit 1320 can also be said to detect the terminal voltage of the secondary battery and manage the charge / discharge state of the secondary battery. For example, to prevent overcharging, it can turn off both the output transistor and the cutoff switch of the charging circuit almost simultaneously.
[0423] FIG. 24B shows an example of a block diagram of the battery pack 1415 shown in FIG.
[0424] The control circuit unit 1320 has at least a switch unit 1324 including a switch for preventing overcharging and a switch for preventing overdischarging, a control circuit 1322 for controlling the switch unit 1324, and a voltage measurement unit for the first battery 1301a. The control circuit unit 1320 is set to an upper limit voltage and a lower limit voltage of the secondary battery to be used, and limits the upper limit of the current from the outside and the upper limit of the output current to the outside. The range between the lower limit voltage and the upper limit voltage of the secondary battery is within the voltage range recommended for use, and when it is outside that range, the switch unit 1324 operates and functions as a protection circuit. In addition, the control circuit unit 1320 can also be called a protection circuit because it controls the switch unit 1324 to prevent overcharging and overdischarging. For example, when the control circuit 1322 detects a voltage that is likely to cause overcharging, the switch unit 1324 is turned off to cut off the current. Furthermore, a PTC element may be provided in the charge / discharge path to provide a function of cutting off the current in response to a rise in temperature. In addition, the control circuit section 1320 has an external terminal 1325 (+IN) and an external terminal 1326 (-IN).
[0425] The switch unit 1324 can be configured by combining n-channel transistors and p-channel transistors. The switch unit 1324 is not limited to a switch having a Si transistor using single crystal silicon, and may be formed of a power transistor having, for example, Ge (germanium), SiGe (silicon germanium), GaAs (gallium arsenide), GaAlAs (gallium aluminum arsenide), InP (indium phosphide), SiC (silicon carbide), ZnSe (zinc selenide), GaN (gallium nitride), GaOx (gallium oxide; x is a real number greater than 0), or the like. Furthermore, since a memory element using an OS transistor can be freely arranged by stacking it on a circuit using a Si transistor, integration can be easily performed. Furthermore, since an OS transistor can be manufactured using the same manufacturing equipment as a Si transistor, it can be manufactured at low cost. That is, a control circuit unit 1320 using an OS transistor can be stacked on the switch unit 1324 and integrated into one chip. Since the volume occupied by the control circuit unit 1320 can be reduced, miniaturization is possible.
[0426] The first batteries 1301a and 1301b mainly supply power to in-vehicle devices of a 42V system (high voltage system), and the second battery 1311 supplies power to in-vehicle devices of a 14V system (low voltage system).
[0427] In this embodiment, an example in which lithium ion secondary batteries are used for both the first battery 1301a and the second battery 1311 is shown. The second battery 1311 may be a lead storage battery, an all-solid-state battery, or an electric double layer capacitor. For example, the all-solid-state battery of Embodiment 5 may be used. By using the all-solid-state battery of Embodiment 5 for the second battery 1311, high capacity can be achieved, and the battery can be made smaller and lighter.
[0428] Moreover, regenerative energy produced by the rotation of the tire 1316 is sent to the motor 1304 via the gear 1305, and is charged into the second battery 1311 via the motor controller 1303 or the battery controller 1302 via the control circuit unit 1321. Alternatively, the first battery 1301a is charged from the battery controller 1302 via the control circuit unit 1320. Alternatively, the first battery 1301b is charged from the battery controller 1302 via the control circuit unit 1320. In order to efficiently charge the regenerative energy, it is desirable that the first batteries 1301a and 1301b are capable of being charged quickly.
[0429] The battery controller 1302 can set the charging voltage and charging current of the first batteries 1301a and 1301b. The battery controller 1302 can set charging conditions in accordance with the charging characteristics of the secondary battery used, and can perform rapid charging.
[0430] Although not shown, when connecting to an external charger, the charger outlet or the connection cable of the charger is electrically connected to the battery controller 1302. The power supplied from the external charger is charged to the first batteries 1301a and 1301b via the battery controller 1302. Some chargers are provided with a control circuit and may not use the function of the battery controller 1302, but it is preferable to charge the first batteries 1301a and 1301b via the control circuit section 1320 to prevent overcharging. In some cases, the connection cable or the connection cable of the charger is provided with a control circuit. The control circuit section 1320 may be called an ECU (Electronic Control Unit). The ECU is connected to a CAN (Controller Area Network) provided in the electric vehicle. The CAN is one of the serial communication standards used as an in-vehicle LAN. The ECU includes a microcomputer. The ECU uses a CPU and a GPU.
[0431] External chargers installed at charging stations and the like include 100V outlets, 200V outlets, and three-phase 200V and 50kW outlets. In addition, charging can also be performed by receiving power from external charging equipment using a contactless power supply system, etc.
[0432] When rapid charging is performed, a secondary battery that can withstand charging at a high voltage is desired in order to charge in a short period of time.
[0433] Moreover, the secondary battery of the present embodiment described above has a high-density positive electrode by using the positive electrode active material 100 obtained in the first embodiment. Furthermore, by using graphene as a conductive additive, a secondary battery with significantly improved electrical characteristics can be realized by suppressing capacity reduction and maintaining a high capacity even when the electrode layer is thickened and the amount of support is increased. This is particularly effective for secondary batteries used in vehicles, and a vehicle with a long driving range, specifically a driving distance of 500 km or more per charge, can be provided without increasing the ratio of the weight of the secondary battery to the total weight of the vehicle.
[0434] In particular, the secondary battery of the present embodiment described above can increase the operating voltage of the secondary battery by using the positive electrode active material 100 described in embodiment 1, and can increase the usable capacity as the charging voltage increases. In addition, by using the positive electrode active material 100 described in embodiment 1 for the positive electrode, a secondary battery for vehicles having excellent cycle characteristics can be provided.
[0435] Next, an example in which the secondary battery according to one embodiment of the present invention is mounted on a vehicle, typically a transportation vehicle, will be described.
[0436] Further, when the secondary battery shown in any one of FIG. 15(D), FIG. 17(C), and FIG. 24(A) is mounted on a vehicle, a next-generation clean energy vehicle such as a hybrid vehicle (HV), an electric vehicle (EV), or a plug-in hybrid vehicle (PHV) can be realized. In addition, the secondary battery can be mounted on transportation vehicles such as agricultural machinery, mopeds including electrically assisted bicycles, motorcycles, electric wheelchairs, electric carts, small or large ships, submarines, aircraft such as fixed-wing aircraft and rotary-wing aircraft, rockets, artificial satellites, space probes, planetary probes, and spacecraft. The secondary battery of one embodiment of the present invention can be a high-capacity secondary battery. Therefore, the secondary battery of one embodiment of the present invention is suitable for miniaturization and weight reduction and can be suitably used for transportation vehicles.
[0437] 25A to 25D show an example of a transportation vehicle using one embodiment of the present invention. An automobile 2001 shown in FIG. 25A is an electric automobile that uses an electric motor as a power source for running. Alternatively, it is a hybrid automobile that can appropriately select and use an electric motor and an engine as a power source for running. When a secondary battery is mounted on a vehicle, an example of the secondary battery described in embodiment 4 is installed in one or more locations. The automobile 2001 shown in FIG. 25A includes a battery pack 2200, which includes a secondary battery module to which a plurality of secondary batteries are connected. It is preferable that the automobile further includes a charge control device that is electrically connected to the secondary battery module.
[0438] Moreover, the automobile 2001 can charge the secondary battery of the automobile 2001 by receiving power supply from an external charging facility by a plug-in method, a contactless power supply method, or the like. When charging, the charging method and connector standards may be appropriately performed by a predetermined method such as CHAdeMO (registered trademark) or Combo. The secondary battery may be a charging station provided in a commercial facility, or may be a home power source. For example, a power storage device mounted on the automobile 2001 can be charged by an external power supply by plug-in technology. Charging can be performed by converting AC power to DC power via a conversion device such as an ACDC converter.
[0439] Although not shown, a power receiving device may be mounted on a vehicle, and charging may be performed by supplying power contactlessly from a ground power transmitting device. In the case of this contactless power supply method, by incorporating a power transmitting device in a road or an exterior wall, charging may be performed not only while the vehicle is stopped but also while the vehicle is moving. This contactless power supply method may also be used to transmit and receive power between two vehicles. Furthermore, a solar cell may be provided on the exterior of the vehicle, and a secondary battery may be charged while the vehicle is stopped or moving. For such contactless power supply, an electromagnetic induction method or a magnetic field resonance method may be used.
[0440] Fig. 25(B) shows a large transport vehicle 2002 having an electrically controlled motor as an example of a transport vehicle. The secondary battery module of the transport vehicle 2002 is a four-cell unit, for example, of secondary batteries of 3.5V or more, preferably 4.7V or more, with 48 cells connected in series to achieve a maximum voltage of 170V. Other than the number of secondary batteries constituting the secondary battery module of the battery pack 2201, it has the same functions as Fig. 25(A), so a description thereof will be omitted.
[0441] FIG. 25(C) shows a large transport vehicle 2003 having an electrically controlled motor as an example. The secondary battery module of the transport vehicle 2003 has a maximum voltage of 600V, for example, with 100 or more secondary batteries of 3.5V or more, preferably 4.7V or more, connected in series. Therefore, a secondary battery with small characteristic variations is required. By using a secondary battery using the positive electrode active material 100 described in the first embodiment as the positive electrode, a secondary battery with stable battery characteristics can be manufactured, and mass production at low cost is possible from the viewpoint of yield. In addition, except for the number of secondary batteries constituting the secondary battery module of the battery pack 2202, the battery pack 2202 has the same functions as those of FIG. 25(A), so description thereof will be omitted.
[0442] Fig. 25(D) shows, as an example, an aircraft 2004 having an engine that burns fuel. Since the aircraft 2004 shown in Fig. 25(D) has wheels for takeoff and landing, it can also be said to be a part of a transportation vehicle, and has a battery pack 2203 including a secondary battery module formed by connecting multiple secondary batteries and a charge control device.
[0443] The secondary battery module of the aircraft 2004 has, for example, eight 4 V secondary batteries connected in series to produce a maximum voltage of 32 V. Other than the number of secondary batteries constituting the secondary battery module of the battery pack 2203, it has the same functions as those in Fig. 25(A), and therefore a description thereof will be omitted.
[0444] This embodiment mode can be used in appropriate combination with other embodiment modes.
[0445] (Embodiment 7) In this embodiment, an example in which a secondary battery according to one embodiment of the present invention is mounted in a building will be described with reference to FIGS. 26A and 26B.
[0446] A house illustrated in FIG. 26A includes a power storage device 2612 including a secondary battery which is one embodiment of the present invention, and a solar panel 2610. The power storage device 2612 is electrically connected to the solar panel 2610 through a wiring 2611 or the like. The power storage device 2612 may be electrically connected to a ground-mounted charging device 2604. The power obtained by the solar panel 2610 can be charged to the power storage device 2612. The power stored in the power storage device 2612 can be charged to a secondary battery included in the vehicle 2603 through the charging device 2604. The power storage device 2612 is preferably installed in an underfloor space. By installing the power storage device 2612 in the underfloor space, the space above the floor can be effectively utilized. Alternatively, the power storage device 2612 may be installed on the floor.
[0447] The power stored in the power storage device 2612 can also be supplied to other electronic devices in the house. Therefore, even when power cannot be supplied from a commercial power source due to a power outage or the like, the electronic devices can be used by using the power storage device 2612 of one embodiment of the present invention as an uninterruptible power supply.
[0448] 26B illustrates an example of a power storage device 700 according to one embodiment of the present invention. As illustrated in FIG. 26B, a power storage device 791 according to one embodiment of the present invention is installed in an underfloor space 796 of a building 799. The power storage device 791 may be provided with the control circuit described in Embodiment 6, and a secondary battery using the positive electrode active material 100 obtained in Embodiment 1 for its positive electrode can be used for the power storage device 891 to obtain a synergistic effect on safety. The control circuit described in Embodiment 6 and the secondary battery using the positive electrode active material 100 described in Embodiment 1 for its positive electrode can greatly contribute to preventing accidents such as fires caused by the power storage device 791 including a secondary battery.
[0449] A control device 790 is installed in the power storage device 791, and the control device 790 is electrically connected to a distribution board 703, a power storage controller 705 (also referred to as a control device), a display 706, and a router 709 by wiring.
[0450] Electric power is sent from a commercial power source 701 to a distribution board 703 via a service line attachment section 710. Electric power is also sent to the distribution board 703 from a power storage device 791 and the commercial power source 701, and the distribution board 703 supplies the sent electric power to a general load 707 and a power storage load 708 via an outlet (not shown).
[0451] The general load 707 is, for example, an electric device such as a television or a personal computer, and the power storage load 708 is, for example, an electric device such as a microwave oven, a refrigerator, or an air conditioner.
[0452] The power storage controller 705 includes a measurement unit 711, a prediction unit 712, and a planning unit 713. The measurement unit 711 has a function of measuring the amount of power consumed by the general load 707 and the power storage load 708 during one day (for example, from 0:00 to 24:00). The measurement unit 711 may also have a function of measuring the amount of power of the power storage device 791 and the amount of power supplied from the commercial power source 701. The prediction unit 712 has a function of predicting the amount of power demand to be consumed by the general load 707 and the power storage load 708 during the next day based on the amount of power consumed by the general load 707 and the power storage load 708 during one day. The planning unit 713 has a function of making a plan for charging and discharging the power storage device 791 based on the amount of power demand predicted by the prediction unit 712.
[0453] The amount of power consumed by the general load 707 and the power storage load 708 measured by the measurement unit 711 can be confirmed by the display 706. In addition, it can also be confirmed on an electric device such as a television or a personal computer via the router 709. Furthermore, it can also be confirmed by a portable electronic terminal such as a smartphone or a tablet via the router 709. In addition, the amount of power demand for each time period (or each hour) predicted by the prediction unit 712 can be confirmed by the display 706, the electric device, and the portable electronic terminal.
[0454] This embodiment mode can be used in appropriate combination with other embodiment modes.
[0455] (Embodiment 8) In this embodiment, an example in which a power storage device according to one embodiment of the present invention is mounted on a motorcycle or a bicycle will be described.
[0456] 27A is an example of an electric bicycle using the power storage device of one embodiment of the present invention. The power storage device of one embodiment of the present invention can be applied to an electric bicycle 8700 shown in FIG. 27A. The power storage device of one embodiment of the present invention includes, for example, a plurality of storage batteries and a protection circuit.
[0457] The electric bicycle 8700 includes a power storage device 8702. The power storage device 8702 can supply electricity to a motor that assists a rider. The power storage device 8702 is portable and is shown in a state removed from the bicycle in FIG. 27B. The power storage device 8702 includes a plurality of built-in storage batteries 8701 of the power storage device of one embodiment of the present invention, and the remaining battery charge and the like can be displayed on a display unit 8703. The power storage device 8702 includes a control circuit 8704 that can control charging or detect an abnormality of the secondary battery, an example of which is shown in Embodiment 6. The control circuit 8704 is electrically connected to the positive and negative electrodes of the storage battery 8701. The control circuit 8704 may be provided with the small solid-state secondary battery shown in FIG. 23A and FIG. 23B. 23(A) and 23(B) in the control circuit 8704, power can be supplied to hold data in a memory circuit of the control circuit 8704 for a long time. In addition, a synergistic effect on safety can be obtained by combining with a secondary battery using the positive electrode active material 100 obtained in Embodiment 1 for the positive electrode. The secondary battery using the positive electrode active material 100 obtained in Embodiment 1 for the positive electrode and the control circuit 8704 can greatly contribute to the elimination of accidents such as fires caused by secondary batteries.
[0458] 27C is an example of a two-wheeled vehicle using a power storage device of one embodiment of the present invention. A scooter 8600 shown in FIG. 27C includes a power storage device 8602, a side mirror 8601, and a turn signal light 8603. The power storage device 8602 can supply electricity to the turn signal light 8603. The power storage device 8602, which includes a plurality of secondary batteries each using the positive electrode active material 100 obtained in Embodiment 1 for its positive electrode, can have a high capacity and contribute to miniaturization.
[0459] 27C, a scooter 8600 can store a power storage device 8602 in an under-seat storage compartment 8604. The power storage device 8602 can be stored in the under-seat storage compartment 8604 even if the under-seat storage compartment 8604 is small in size.
[0460] (Embodiment 9) In this embodiment, an example of mounting a secondary battery according to one embodiment of the present invention in an electronic device will be described. Examples of electronic devices mounting a secondary battery include television devices (also called televisions or television receivers), monitors for computers, digital cameras, digital video cameras, digital photo frames, mobile phones (also called mobile phones or mobile phone devices), portable game machines, portable information terminals, audio playback devices, and large game machines such as pachinko machines. Examples of portable information terminals include notebook personal computers, tablet terminals, e-books, and mobile phones.
[0461] 28A shows an example of a mobile phone. The mobile phone 2100 includes a display unit 2102 built into a housing 2101, an operation button 2103, an external connection port 2104, a speaker 2105, a microphone 2106, and the like. The mobile phone 2100 includes a secondary battery 2107. By including the secondary battery 2107 using the positive electrode active material 100 described in the first embodiment as a positive electrode, a high capacity can be achieved, and a configuration that can accommodate space saving associated with a miniaturized housing can be realized.
[0462] The mobile phone 2100 is capable of executing a variety of applications, such as mobile phone calls, e-mail, document browsing and creation, music playback, Internet communications, and computer games.
[0463] The operation button 2103 can have various functions, such as time setting, power on / off operation, wireless communication on / off operation, silent mode activation / cancellation, power saving mode activation / cancellation, etc. For example, the function of the operation button 2103 can be freely set by an operating system built into the mobile phone 2100.
[0464] The mobile phone 2100 is also capable of performing short-range wireless communication according to a communication standard. For example, the mobile phone 2100 can communicate with a wireless headset to enable hands-free calling.
[0465] The mobile phone 2100 also includes an external connection port 2104, and can directly exchange data with other information terminals via a connector. Charging can also be performed via the external connection port 2104. Note that charging may be performed by wireless power supply without using the external connection port 2104.
[0466] It is preferable that the mobile phone 2100 has a sensor. For example, it is preferable that a human body sensor such as a fingerprint sensor, a pulse sensor, a body temperature sensor, a touch sensor, a pressure sensor, an acceleration sensor, or the like is mounted as the sensor.
[0467] FIG. 28(B) shows an unmanned aerial vehicle 2300 having a plurality of rotors 2302. The unmanned aerial vehicle 2300 is sometimes called a drone. The unmanned aerial vehicle 2300 includes a secondary battery 2301 which is one embodiment of the present invention, a camera 2303, and an antenna (not shown). The unmanned aerial vehicle 2300 can be remotely controlled via the antenna. A secondary battery using the positive electrode active material 100 obtained in Embodiment 1 for a positive electrode has high energy density and high safety, and therefore can be used safely for a long period of time and is suitable as a secondary battery to be mounted on the unmanned aerial vehicle 2300.
[0468] Fig. 28(C) shows an example of a robot. The robot 6400 shown in Fig. 28(C) includes a secondary battery 6409, an illuminance sensor 6401, a microphone 6402, an upper camera 6403, a speaker 6404, a display unit 6405, a lower camera 6406, an obstacle sensor 6407, a moving mechanism 6408, a computing device, and the like.
[0469] The microphone 6402 has a function of detecting the user's voice, environmental sounds, etc. The speaker 6404 has a function of emitting sound. The robot 6400 can communicate with the user using the microphone 6402 and the speaker 6404.
[0470] The display unit 6405 has a function of displaying various information. The robot 6400 can display information desired by the user on the display unit 6405. The display unit 6405 may be equipped with a touch panel. The display unit 6405 may also be a removable information terminal, and by installing it in a fixed position on the robot 6400, charging and data transfer are possible.
[0471] The upper camera 6403 and the lower camera 6406 have a function of capturing images of the surroundings of the robot 6400. In addition, the obstacle sensor 6407 can detect the presence or absence of an obstacle in the moving direction when the robot 6400 moves forward using the moving mechanism 6408. The robot 6400 can recognize the surrounding environment and move safely using the upper camera 6403, the lower camera 6406, and the obstacle sensor 6407.
[0472] The robot 6400 includes a secondary battery 6409 according to one embodiment of the present invention and a semiconductor device or an electronic component in an internal region thereof. A secondary battery using the positive electrode active material 100 obtained in Embodiment 1 for a positive electrode has high energy density and high safety, and therefore can be used safely for a long period of time. Thus, the secondary battery is suitable as the secondary battery 6409 to be mounted on the robot 6400.
[0473] 28(D) shows an example of a cleaning robot. The cleaning robot 6300 has a display unit 6302 arranged on the top surface of a housing 6301, a plurality of cameras 6303 arranged on the side surface, a brush 6304, an operation button 6305, a secondary battery 6306, various sensors, and the like. Although not shown, the cleaning robot 6300 is provided with tires, a suction port, and the like. The cleaning robot 6300 can move by itself, detect dust 6310, and suck up the dust from a suction port arranged on the bottom surface.
[0474] For example, the cleaning robot 6300 can analyze an image captured by the camera 6303 and determine the presence or absence of an obstacle such as a wall, furniture, or a step. When an object that may be entangled in the brush 6304, such as a wire, is detected by image analysis, the rotation of the brush 6304 can be stopped. The cleaning robot 6300 includes a secondary battery 6306 according to one embodiment of the present invention and a semiconductor device or an electronic component in an internal region thereof. The secondary battery using the positive electrode active material 100 obtained in Embodiment 1 for the positive electrode has high energy density and high safety, and therefore can be used safely for a long period of time and is suitable as the secondary battery 6306 to be mounted on the cleaning robot 6300.
[0475] Figure 29(A) shows an example of a wearable device. Wearable devices use secondary batteries as a power source. In order to increase water resistance in daily use or outdoor use, there is a demand for wearable devices that can be charged wirelessly as well as by wires with exposed connectors.
[0476] For example, the secondary battery according to one embodiment of the present invention can be mounted on a glasses-type device 4000 as shown in FIG. 29A. The glasses-type device 4000 has a frame 4000a and a display portion 4000b. By mounting a secondary battery on temple portions of the curved frame 4000a, the glasses-type device 4000 can be lightweight, well-balanced in weight, and capable of long continuous use. The secondary battery using the positive electrode active material 100 obtained in Embodiment 1 for its positive electrode has a high energy density, and a configuration that can accommodate space saving associated with a miniaturized housing can be realized.
[0477] Furthermore, the secondary battery according to one embodiment of the present invention can be mounted on the headset type device 4001. The headset type device 4001 has at least a microphone unit 4001a, a flexible pipe 4001b, and an earphone unit 4001c. The secondary battery can be provided in the flexible pipe 4001b or the earphone unit 4001c. The secondary battery using the positive electrode active material 100 obtained in Embodiment 1 for the positive electrode has a high energy density, and a configuration that can accommodate space saving associated with miniaturization of the housing can be realized.
[0478] Furthermore, the secondary battery according to one embodiment of the present invention can be mounted on a device 4002 that can be directly attached to the body. A secondary battery 4002b can be provided in a thin housing 4002a of the device 4002. A secondary battery using the positive electrode active material 100 obtained in Embodiment 1 for its positive electrode has high energy density, and a structure that can accommodate space saving associated with a miniaturized housing can be realized.
[0479] Furthermore, the secondary battery according to one embodiment of the present invention can be mounted on a device 4003 that can be attached to clothing. A secondary battery 4003b can be provided in a thin housing 4003a of the device 4003. A secondary battery using the positive electrode active material 100 obtained in Embodiment 1 for its positive electrode has high energy density, and a structure that can accommodate space saving associated with a miniaturized housing can be realized.
[0480] Furthermore, the secondary battery according to one embodiment of the present invention can be mounted on the belt type device 4006. The belt type device 4006 has a belt portion 4006a and a wireless power receiving portion 4006b, and a secondary battery can be mounted in an inner region of the belt portion 4006a. The secondary battery using the positive electrode active material 100 obtained in Embodiment 1 for the positive electrode has a high energy density, and a configuration that can accommodate space saving associated with miniaturization of the housing can be realized.
[0481] Furthermore, the secondary battery according to one embodiment of the present invention can be mounted on the wristwatch device 4005. The wristwatch device 4005 has a display portion 4005a and a belt portion 4005b, and the secondary battery can be provided on the display portion 4005a or the belt portion 4005b. The secondary battery using the positive electrode active material 100 obtained in Embodiment 1 for its positive electrode has high energy density, and a structure that can accommodate space saving associated with miniaturization of the housing can be realized.
[0482] The display unit 4005a can display not only the time, but also various other information such as incoming e-mails and phone calls.
[0483] In addition, since the wristwatch type device 4005 is a wearable device that is directly wrapped around the arm, it may be equipped with sensors that measure the user's pulse, blood pressure, etc. Data on the user's amount of exercise and health can be accumulated to manage the user's health.
[0484] FIG. 29(B) shows a perspective view of the wristwatch type device 4005 removed from the wrist.
[0485] 29C shows a side view. Fig. 29C shows a state in which a secondary battery 913 is built in the internal region. The secondary battery 913 is the secondary battery described in Embodiment 4. The secondary battery 913 is provided at a position overlapping with the display portion 4005a, and can have high density and high capacity, and is small and lightweight.
[0486] Since the wristwatch type device 4005 is required to be small and lightweight, by using the positive electrode active material 100 obtained in embodiment 1 for the positive electrode of the secondary battery 913, the secondary battery 913 can have a high energy density and be small in size.
[0487] This embodiment mode can be implemented in appropriate combination with other embodiment modes. EXAMPLES
[0488] <Production and evaluation of secondary batteries> A secondary battery was fabricated using the positive electrode active material of the comparative example obtained according to the fabrication flow of the third embodiment and the sample of the present embodiment. First, the positive electrode active material of the comparative example and the sample of the present embodiment was used, and for each sample, acetylene black (AB) and polyvinylidene fluoride (PVDF) were mixed in a ratio of active material:AB:PVDF=95:3:2 (weight ratio) to prepare a slurry, and the slurry was applied to an aluminum current collector. NMP was used as the solvent for the slurry. PVDF is a resin having a melting point in the range of 134°C to 169°C, and is a material with excellent thermal stability.
[0489] After the slurry was applied to the current collector, the solvent was evaporated. Then, pressure was applied at 210 kN / m, and then pressure was applied at 1467 kN / m. A positive electrode was obtained by the above process. The amount of the positive electrode loaded was about 7 mg / cm. 2 The density was 3.8 g / cc or more.
[0490] Using the prepared positive electrode, a coin-type battery cell of the CR2032 type (diameter 20 mm, height 3.2 mm) was produced.
[0491] Lithium metal was used as the counter electrode.
[0492] The second electrolyte contained in the first electrolyte, which was the solvent, was 1 mol / L lithium hexafluorophosphate (LiPF6), and the first electrolyte was a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of EC:DEC = 3:7, to which 2 wt% vinylene carbonate (VC) was added.
[0493] The separator was made of polypropylene having a thickness of 25 μm.
[0494] The positive electrode can and the negative electrode can were made of stainless steel (SUS).
[0495] As a positive electrode active material containing cobalt as the transition metal M and not containing any particular impurities, a commercially available lithium cobalt oxide (Cellseed C-10N, manufactured by Nippon Chemical Industry Co., Ltd.) was used as a comparative example.
[0496] The cycle characteristics of the secondary batteries of the comparative example and the sample of this embodiment are shown in FIG. 13. Both were measured at 45° C. The charge was CC / CV (0.5 C, 4.6 V, 0.05 C cut), and the discharge was CC (0.5 C, 2.5 V cut), with a 10-minute rest period before the next charge. In this embodiment, 1 C was 200 mA / g.
[0497] The sample of this embodiment having magnesium and fluorine as added elements (or impurities) exhibited good cycle characteristics even at a relatively high temperature of 45°C.
[0498] The sample of the present embodiment having the protrusions scattered on the surface of the positive electrode active material had a larger discharge capacity than the comparative example. For example, the discharge capacity of the comparative example was 215.5 mAh / g, whereas the discharge capacity of the sample of the present embodiment was 227.2 mAh / g.
[0499] In the sample of the present embodiment containing titanium as an impurity, the surface of the positive electrode active material is dotted with projections, and some or all of the projections have electric field relaxation regions containing titanium, which is believed to reduce the potential difference at the interface between the electrolyte and the positive electrode active material.
[0500] In the sample of this embodiment, the presence of the electric field relaxation region where excess additive elements (or impurities) are unevenly distributed removes excess impurities such as magnesium from the main body, and the metal element concentration inside is appropriate. Therefore, it is considered that the resistance when used as a secondary battery is suppressed and the discharge capacity is increased. [Explanation of symbols]
[0501] 100 Cathode active material 100a Near-surface region 100b internal area 100c Top layer 100d High Nickel Concentration Area 101 Grain Boundary 103 Electric field relaxation region 103a High fluorine concentration area 103b Metal element high concentration region 104 Cathode active material 105 Cathode active material 106 Mixed area 300 Secondary battery 301 Positive electrode can 302 Anode can 303 Gasket 304 Positive electrode 305 Positive electrode current collector 306 Positive electrode active material layer 307 Negative electrode 308 Negative electrode current collector 309 Negative electrode active material layer 310 Separator 400 Secondary battery 410 Positive electrode 411 Cathode active material 413 Positive electrode current collector 414 Cathode active material layer 420 Solid electrolyte layer 421 Solid electrolyte 430 negative electrode 431 Negative electrode active material 433 Negative electrode current collector 434 Negative electrode active material layer 500 secondary battery 501 Positive electrode current collector 502 Positive electrode active material layer 503 Positive electrode 504 Negative electrode current collector 505 Negative electrode active material layer 506 negative electrode 507 Separator 508 Electrolyte 509 Exterior body 510 Positive lead electrode 511 Negative lead electrode 513 Secondary battery 514 Terminal 515 Seal 517 Antenna 519 layers 529 Label 530 Oxide 531 Secondary battery pack 540 Circuit Board 550 Current collector 551 On the other hand 552 On the other hand 553 Acetylene Black 554 Graphene 555 Carbon Nanotubes 561 Active material 562 Active material 590 Control Circuit 590a Circuit System 590b Circuit System 600 Secondary battery 601 Positive electrode cap 602 Battery Can 603 Positive terminal 604 Positive electrode 605 Separator 606 negative electrode 607 Negative terminal 608 Insulating plate 609 Insulating plate 611 PTC element 613 Safety valve mechanism 614 Conductive plate 615 Energy Storage System 616 Secondary battery 620 Control circuit 621 Wiring 622 Wiring 623 Wiring 624 Conductors 625 Insulators 626 Wiring 627 Wiring 628 Conductive plate 700 Energy storage device 701 Commercial power supply 703 Distribution Board 705 Storage Controller 706 Display 707 General load 708 Storage Load 709 Router 710 Drop line attachment part 711 Measurement Division 712 Prediction Department 713 Planning Department 750a positive electrode 750b solid electrolyte layer 750c negative pole 751 Electrode Plate 752 Insulating tube 753 Electrode Plate 761 Lower member 762 Upper member 764 Wing Nut 765 O-ring 766 Insulators 770a Packaging material 770b Packaging material 770c packaging material 771 External electrode 772 External electrode 773a Electrode layer 773b Electrode layer 790 Control Device 791 Energy storage device 796 Underfloor space 799 Building 911a Terminal 911b Terminal 913 Secondary battery 930 Case 930a Case 930b Case 931 negative electrode 931a Negative electrode active material layer 932 Positive electrode 932a Cathode active material layer 933 Separator 950 Wound body 950a Wound body 951 Terminal 952 Terminal 1300 Square rechargeable battery 1301a Battery 1301b Battery 1302 Battery Controller 1303 Motor Controller 1304 Motor 1305 Gear 1306 DC-DC circuit 1307 Electric power steering 1308 Heater 1309 Defogger 1310 DC-DC circuit 1311 Battery 1312 Inverter 1313 Audio 1314 Power window 1315 Lamps 1316 Tires 1317 Rear motor 1320 Control circuit section 1321 Control circuit section 1322 Control circuit 1324 Switch section 1325 External terminal 1326 External terminal 1400 Battery 1402 Positive electrode 1404 Negative electrode 1413 Fixed part 1414 Fixed part 1415 Battery Pack 1421 Wiring 1422 Wiring 2001 Automobiles 2002 Transport vehicle 2003 Transport Vehicles 2004 aircraft 2100 Mobile phone 2101 Case 2102 Display section 2103 Operation button 2104 External connection port 2105 Speaker 2106 Mike 2107 Secondary battery 2200 Battery Pack 2201 Battery Pack 2202 Battery Pack 2203 Battery Pack 2300 Unmanned Aircraft 2301 Secondary battery 2302 Rotor 2303 Camera 2603 Vehicles 2604 Charging device 2610 Solar Panel 2611 Wiring 2612 Energy storage device 4000 Glasses-type device 4000a Frame 4000b Display section 4001 Headset type device 4001a Microphone section 4001b Flexible Pipe 4001c Earphones 4002 Devices 4002a Case 4002b secondary battery 4003 Device 4003a Case 4003b secondary battery 4005 Wristwatch-type device 4005a Display section 4005b Belt section 4006 Belt-type device 4006a Belt section 4006b Wireless power receiving unit 6300 Cleaning robot 6301 Case 6302 Display section 6303 Camera 6304 Brush 6305 Operation button 6306 Secondary battery 6310 Garbage 6400 Robot 6401 Light Sensor 6402 Microphone 6403 Upper Camera 6404 Speaker 6405 Display section 6406 Lower Camera 6407 Obstacle Sensor 6408 Moving mechanism 6409 Secondary battery 8600 Scooter 8601 Side mirror 8602 Energy storage devices 8603 Turn signal light 8604 Under-seat storage 8700 Electric Bike 8701 Storage battery 8702 Energy storage devices 8703 Display section 8704 Control circuit
Claims
1. A secondary battery having a positive electrode, an electrolyte, and a negative electrode, The positive electrode has a positive electrode active material, the positive electrode active material has an interior, a first region near a surface, and a second region in contact with a part of the first region, the second region has a region located closer to a surface side of the positive electrode active material than the first region, the first region comprises fluorine, magnesium, and aluminum; the second region has one or more elements selected from hafnium, zirconium, yttrium, barium, titanium, lead, scandium, strontium, bismuth, and tantalum; A secondary battery, wherein, in EDX ray analysis, a magnesium concentration peak in the first region is closer to a surface than an aluminum concentration peak in the first region.
2. A secondary battery having a positive electrode, an electrolyte, and a negative electrode, The positive electrode has a positive electrode active material, the positive electrode active material has an interior, a first region near a surface, and a second region in contact with a part of the first region, the second region has a region located closer to a surface side of the positive electrode active material than the first region, the first region comprises fluorine, magnesium, aluminum, and nickel; the second region has one or more elements selected from hafnium, zirconium, yttrium, barium, titanium, lead, scandium, strontium, bismuth, and tantalum; A secondary battery, wherein, in EDX ray analysis, a magnesium concentration peak in the first region is closer to a surface than an aluminum concentration peak in the first region.
3. In claim 1 or 2, A secondary battery, wherein one or both of the first region and the second region cover a part or all of the interior.
4. In claim 1 or 2, A secondary battery, wherein one or both of the first region and the second region are scattered in an island shape.
5. In any one of claims 1 to 4, A secondary battery, wherein either or both of the first region and the second region have ferroelectricity.
6. In any one of claims 1 to 5, The inside of the secondary battery is made of one or more composite oxides selected from the group consisting of lithium, cobalt, manganese, nickel, aluminum, and iron.
7. In any one of claims 1 to 6, The secondary battery, wherein one or more of the positive electrode, the electrolyte, and the negative electrode comprises graphene.
Citation Information
Patent Citations
Positive electrode material for lithium secondary battery, lithium secondary battery, and secondary battery module using the same
JP2010232001A
Nonaqueous electrolyte secondary battery
JP2011210694A
Positive electrode material for nonaqueous secondary battery and manufacturing method thereof, and positive electrode for nonaqueous secondary battery using positive electrode material for nonaqueous secondary battery and nonaqueous secondary battery using the same
JP2016096075A
Cathode active material, manufacture method of cathode active material, and secondary battery
JP2018088400A
Active material particle, cathode with active material particle, power storage device with cathode and manufacturing method thereof
JP2018110065A